Laminate, display device, and member for laminate
By increasing the nanoindentation method recovery rate of the second layer in the laminate, the peeling and crack problems of the laminated body during repeated bending in the flexible display device are solved, and good bending resistance is achieved.
Patent Information
- Application Number
- CN202380048783.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-29
- Filing Date
- 2023-06-29
- Publication Date
- 2025-02-07
AI Technical Summary
In flexible display devices, the laminated body is prone to peeling and cracking when it is repeatedly bent, especially when the bending load is concentrated in the local area.
By designing the cross-section of the second layer, the recovery rate of the nano-indentation method is above 10%, ensuring that the second layer can effectively restore shape when bending, reduce shear stress, and thus inhibit peeling.
It is achieved that good bending resistance can be maintained even when the bending part is local, and peeling and cracking of the laminated body during repeated bending is avoided.
Smart Images

Figure CN119403675A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a laminate, a display device, and a member for a laminate. Background Art
[0002] Conventionally, for example, in display devices, a cover member made of glass or resin is used to protect the display device. The glass cover member has the characteristics of high surface hardness, being hard to be scratched, and having high transparency, while the resin cover member has the characteristics of being light and hard to be broken.
[0003] In recent years, the development of flexible displays such as foldable displays, rollable displays, and bendable displays has been actively progressing, and among them, the development of foldable displays, that is, bendable display devices, has been progressing.
[0004] In a bendable display device, the cover part also needs to bend following the movement of the display device, so a bendable cover part is applied. In the case of a resin cover part, a colorless and transparent polyimide or polyamide-imide film has been developed by designing the chemical structure. In addition, in the case of a glass cover part, research is being conducted on cover parts such as ultra-thin glass (UTG) that are bendable by thinning the glass. Among glasses, glass with particularly high bending resistance is called chemically strengthened glass, which internalizes the stress of expansion on the glass surface so that the tiny damage on the glass surface does not become larger when bent, making the glass less likely to break.
[0005] For example, Patent Document 1 discloses an optical layered body which sequentially comprises a front panel, a predetermined first adhesive layer formed using a first adhesive composition, a polarizer, a predetermined second adhesive layer formed using a second adhesive composition, and a back panel, wherein a resin film having a glass plate and a hard coating layer is disclosed as the front panel.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Publication No. 2021-140147 Summary of the invention
[0009] Problems to be solved by the invention
[0010] In a flexible display device, a foldable display is required to have no display defects even when bent repeatedly, and a laminate disposed on the surface of the flexible display device is required to have bending resistance that does not cause peeling or cracking when bent repeatedly. In the past, a test for evaluating the bending resistance of a laminate was generally used. Fig.14 In the U-bend test, for example, Fig.14As shown in (a), the short side 10P of the laminate 10 and the short side 10Q facing the short side 10P are fixed by the fixing parts 100A and 100B arranged in parallel. Fig.14 As shown in (a), the fixing portion 100B can slide in the horizontal direction. Fig.14 As shown in (b) to (c) of FIG. 1 , the laminate 10 is bent into a U-shape by moving the fixing portion 100B so as to approach the fixing portion 100A. In such a U-shaped bending test, Fig.14 As shown in (a) to (c) of FIG. 1 , the sample (laminate 10 ) is bent into a U-shape by moving the fixing portion 100B so as to approach the fixing portion 100A. Therefore, a bending load is applied to the entire sample (laminate 10 ).
[0011] On the other hand, when a foldable display is actually used, sometimes the bending portion is local, and sometimes the stress is concentrated on the local bending portion. The inventors of the present disclosure have found that even for a laminate evaluated as having good bending resistance in a U-shaped bending test, the bending load is concentrated on the local bending portion, and when such bending is repeated, there is a problem of peeling between the layers constituting the laminate. Specifically, it was found that: in a laminate having a first layer, a second layer, and a third layer, and the second layer joins the first layer to the third layer, sometimes the second layer peels off from the first layer or the third layer. In addition, in a laminate having a first layer, a second layer, a fourth layer, and a third layer, and the second layer and the fourth layer join the first layer to the third layer, when the bending portion is local and is repeatedly bent, there is a problem of the second layer peeling off from the first layer, or the third layer peeling off from the fourth layer.
[0012] It should be noted that Patent Document 1 states that in order to suppress the generation of bubbles in the adhesive layer when the optical layered body is bent and maintained in this state for a certain period of time, the shear recovery rates of the first adhesive layer and the second adhesive layer based on a viscoelasticity measuring device are set within a predetermined range. However, there is no description of the problem of peeling of the adhesive layer caused when the bending load is repeatedly concentrated on a local bending portion as described above.
[0013] The present disclosure has been made in view of the above-mentioned actual situation, and a main object of the present disclosure is to provide a laminate having excellent bending resistance even when the bent portion is local.
[0014] Means for solving problems
[0015] One embodiment of the present disclosure provides a laminate including a first layer, a second layer, and a third layer in this order, wherein a recovery rate of a cross section of the second layer as determined by a nanoindentation method is 10% or more.
[0016] One embodiment of the present disclosure provides a laminate including a first layer, a second layer, a fourth layer, and a third layer in this order, wherein a recovery rate of each cross section of the second layer and the fourth layer based on a nanoindentation method is 10% or more.
[0017] Furthermore, there is provided a display device including: a display panel; and the laminated body disposed on a viewer's side of the display panel.
[0018] Furthermore, there is provided a laminate component used for the laminate, wherein the laminate component is formed by laminating the first layer and the second layer.
[0019] Effects of the Invention
[0020] The present disclosure has an effect of being able to provide a laminate having excellent bending resistance even when the bent portion is local. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a schematic cross-sectional view illustrating a laminate in the first embodiment of the present disclosure.
[0022] Figure 2 This is a schematic cross-sectional view illustrating a laminate in the first embodiment of the present disclosure.
[0023] Figure 3 This is a schematic cross-sectional view illustrating a laminate in the first embodiment of the present disclosure.
[0024] Figure 4 This is a schematic cross-sectional view illustrating a laminate in the first embodiment of the present disclosure.
[0025] Figure 5 This is a schematic cross-sectional view illustrating a laminate in the first embodiment of the present disclosure.
[0026] Figure 6 This is a schematic cross-sectional view illustrating a laminate in the second embodiment of the present disclosure.
[0027] Figure 7 This is a schematic cross-sectional view illustrating a laminate in the second embodiment of the present disclosure.
[0028] Figure 8 This is a schematic cross-sectional view illustrating a laminate in the second embodiment of the present disclosure.
[0029] Fig. 9 This is a schematic cross-sectional view illustrating a laminate in the second embodiment of the present disclosure.
[0030] Fig.10This is a schematic cross-sectional view illustrating a laminate in the second embodiment of the present disclosure.
[0031] Fig.11 is a schematic cross-sectional view illustrating a display device in the present disclosure.
[0032] Fig.12 It is a schematic cross-sectional view illustrating a member for a laminate in the present disclosure.
[0033] Fig.13 It is the load-displacement curve measured by the indentation method.
[0034] Fig.14 This is a schematic diagram for explaining the U-shaped bending test.
[0035] Fig.15 is a schematic diagram for explaining the clamshell bending test.
[0036] Fig.16 This is a schematic diagram for explaining an impact test. DETAILED DESCRIPTION
[0037] Hereinafter, the embodiments of the present disclosure will be described with reference to the accompanying drawings, etc. Among them, the present disclosure can be implemented in a variety of different ways, and is not to be construed as being limited to the contents of the embodiments illustrated below. In addition, in order to make the description clearer, the drawings sometimes schematically represent the width, thickness, shape, etc. of each part compared to the actual situation, but this is always an example and does not limit the interpretation of the present disclosure. In addition, in this specification and the drawings, the same figure marks are given to the same elements as the above-mentioned elements in the drawings that have already appeared, and the detailed description is sometimes appropriately omitted.
[0038] In this specification, when describing a method of arranging another component above a certain component, if it is simply described as "above" or "below", unless otherwise stated, it includes both the case where the other component is arranged directly above or directly below in a manner of contacting the certain component, and the case where the other component is arranged above or below the certain component with another component further interposed therebetween. In addition, in this specification, when describing a method of arranging another component on the surface of a certain component, if it is simply described as "surface side" or "surface", unless otherwise stated, it includes both the case where the other component is arranged directly above or directly below in a manner of contacting the certain component, and the case where the other component is arranged above or below the certain component with another component further interposed therebetween.
[0039] Hereinafter, the laminate, the display device, and the laminate member in the present disclosure will be described in detail.
[0040] A-1. Laminated body (first embodiment)
[0041] The laminate in the first embodiment of the present disclosure is a laminate having a first layer, a second layer, and a third layer in this order, and the recovery rate of the cross section of the second layer by the nanoindentation method is equal to or greater than a predetermined value.
[0042] Figure 1 Schematic cross-sectional view showing an example of a laminate according to the first embodiment of the present disclosure. Figure 1 As shown, the laminate 10A in this embodiment has a thickness direction D T The first layer 1, the second layer 2, and the third layer 3 are sequentially provided thereon. In the present embodiment, the recovery rate of the cross section of the second layer 2 by the nanoindentation method is equal to or greater than a predetermined value.
[0043] As described above, for example, in the case of a foldable display, when a laminate having a first layer, a second layer, and a third layer, in which the second layer joins the first layer and the third layer, is repeatedly bent in a case where the bending portion is local, there is a problem that the second layer is peeled off from the first layer or the third layer. Regarding this phenomenon, it is believed that the harder the layer (for example, a layer with a high complex elastic modulus), the higher the shear stress concentrated on the bending portion, and therefore the more likely it is to peel off.
[0044] However, the inventors of the present disclosure have found that the ease with which the second layer peels off does not depend on the complex elastic modulus. In addition, the inventors of the present disclosure have conducted in-depth research and found that by making the recovery rate of the cross section of the second layer based on the nanoindentation method greater than a specified value, the peeling of the second layer can be suppressed even when the bending portion is local, and the bending resistance becomes good.
[0045] This is presumably based on the following reasons. That is, in the bending action of the curved portion, when the second layer transfers from a flat surface to a bent state, it is displaced in the stretched direction (hereinafter referred to as tensile displacement), and when it returns to the flat surface from the bent state, it is displaced in the compressed direction (hereinafter referred to as compressive displacement). Here, during the above displacement, when the recovery rate is extremely high, shear stress is applied during the initial tensile displacement, but during the subsequent compressive displacement, there is sufficient force to restore to the original shape, so it can be imagined that the shear stress will not be applied greatly. Furthermore, it is assumed that the same state continues in the subsequent bending. That is, when the recovery rate of the second layer is high, it is difficult to peel off even when the composite elastic modulus of the second layer is high.
[0046] On the other hand, when the recovery rate is low, the same shear stress as above is applied during the initial tensile displacement, but plastic deformation occurs in the bent state during the subsequent compressive displacement, so shear stress is also applied during the compressive displacement as the original shape. In addition, it is also assumed that the same shear stress is continuously applied during the subsequent bending.
[0047] In particular, when a local bending motion with a small curvature radius continues, it is expected that the above-mentioned shear stress application mode becomes remarkable.
[0048] From the above, it is inferred that, when the bending is local, if the recovery rate of the cross section of the second layer by the nanoindentation method is equal to or greater than a predetermined value, separation is unlikely to occur.
[0049] Hereinafter, the laminated body according to the first embodiment of the present disclosure will be described in detail for each layer.
[0050] 1. Layer 2
[0051] The second layer in this embodiment is disposed between the first layer and the third layer, and has a function as a bonding layer for bonding the first layer to the third layer. In this embodiment, the recovery rate of the cross section of the second layer in the thickness direction based on the nanoindentation method is greater than a predetermined value. The cross section of the second layer in the thickness direction refers to the cross section of the second layer in the thickness direction D. T The cross section is obtained by cutting (in the stacking direction of the stack).
[0052] (1) Recovery rate based on nanoindentation method
[0053] The recovery rate of the cross section of the second layer based on the nanoindentation method is usually 10% or more, can be 20% or more, can be 30% or more, can be 40% or more, and can be 50% or more. On the other hand, the above recovery rate is, for example, 80% or less, can be 70% or less, and can be 60% or less.
[0054] Specifically, it is preferably in the range of 10% to 80%, more preferably in the range of 20% to 70%, and particularly preferably in the range of 30% to 60%.
[0055] The “recovery rate” in the present disclosure refers to a value obtained by a nanoindentation method from a load-displacement curve measured using a surface film physical property tester (Triboindenter TI950, manufactured by BRUKER).
[0056] The load-displacement curve is obtained as follows: for the cross-section in the thickness direction of the second layer in the measurement sample produced by the following method, a Berkovich indenter (material: diamond triangular pyramid) is pressed (pressed) in the vertical direction under the following conditions, and the relationship between the load and the displacement is measured until the indenter is removed (unloading). Fig.13 A general load-displacement curve is shown.
[0057] <Measurement Sample Preparation Method>
[0058] First, a block is prepared by embedding a laminate cut into 1 mm × 10 mm with an embedding resin, and a uniform slice having a thickness of 50 nm to 100 nm without holes or the like is cut from the block using a general slice making method. The slices can be made using an "Ultramicrotome EMUC7" (manufactured by Leica Microsystems) or the like. Then, the block remaining after the uniform slice without holes or the like is cut out is used as a measurement sample.
[0059] Next, in the cross section obtained by cutting out the above-mentioned slice in this measurement sample, under the following measurement conditions, the Berkovich indenter (triangular pyramid, TI-0039 manufactured by BRUKER) as the above-mentioned indenter is vertically pressed into the center of the cross section of the second layer with a maximum indentation load of 25 μN for 10 seconds. After that, after keeping it fixed to relieve the residual stress, it takes 10 seconds to unload. Here, the position where the Berkovich indenter is pressed is preferably the approximate center in the thickness direction of the second layer. Approximately the center means that when the thickness of the second layer is defined as T [μm], the deviation from the center in the thickness direction of the second layer is within ±0.1T. Specifically, the deviation from the center in the thickness direction of the second layer is preferably ±0.1μm.
[0060] <Load-displacement curve measurement conditions>
[0061] ·Indenter used: Burkovich indenter (triangular pyramid, model: TI-0039, manufactured by BRUKER)
[0062] ·Pressing conditions: load control method
[0063] (Measurement Condition 1)
[0064] Maximum load: 25μN
[0065] Load application time: 10 seconds (0μN→25μN speed: 2.5μN / sec)
[0066] Hold time: 5 seconds
[0067] Load unloading time: 10 seconds (25μN→0μN speed: -2.5μN / sec)
[0068] In addition, when the measurement is performed under the above-mentioned measurement condition 1, if the indentation depth under the maximum load is 500 nm or more, the measurement is changed to the following measurement condition 2.
[0069] (Measurement Condition 2)
[0070] Maximum load: 3μN
[0071] Load application time: 10 seconds (0μN→3μN, speed: 0.3μN / second)
[0072] Hold time: 5 seconds
[0073] Load unloading time: 10 seconds (3μN→0μN, speed: -0.3μN / second)
[0074] ※ When pressing after applying a load, adjust the holding time within the range of 5 seconds → 50 seconds.
[0075] The displacement after unloading and the maximum displacement are calculated from the obtained load-displacement curve data. Fig.13 The load-displacement curve shows the displacement after unloading and the maximum displacement. The recovery rate is calculated from the displacement after unloading and the maximum displacement according to the following formula.
[0076] Recovery rate [%] = (displacement after unloading / maximum displacement) × 100
[0077] The recovery rate in this specification is a value measured at a temperature of 23±5° C. and a relative humidity of 40 to 65%. The recovery rate is the arithmetic mean of the recovery rates obtained at 10 cross sections of the second layer of the laminate.
[0078] Examples of methods for making the recovery rate of the cross section of the second layer by nanoindentation method 10% or more include increasing the molecular weight of the resin, increasing the breaking strength of the resin, increasing the breaking elongation of the resin, and increasing the glass transition temperature (Tg) of the resin.
[0079] (2) Composite elastic modulus
[0080] The composite elastic modulus of the second layer in the present embodiment may be, for example, 0.01 GPa or more, preferably 0.05 GPa or more, and more preferably greater than 0.05 GPa. If the composite elastic modulus of the second layer is greater than the above value, the damage resistance of the laminate is improved, so it is preferred. In addition, the composite elastic modulus of the second layer is, for example, 7.0 GPa or less, and may also be 6.0 GPa or less.
[0081] The complex elastic modulus of the second layer in this embodiment is obtained by analyzing the load-displacement curve prepared by the above method, using the contact projection area A p It is calculated by the following formula (1). In the present specification, the complex elastic modulus of the second layer refers to the arithmetic mean of 10 measured values. The complex elastic modulus is measured at a temperature of 23°C ± 5°C and a humidity of 40 to 65%.
[0082] [Number 1]
[0083]
[0084] (In the above formula (1), A p is the contact projection area, E r is the composite elastic modulus of the second layer, S is the contact rigidity, and is the slope of the unloading curve. )
[0085] (3) Indentation hardness H IT / Complex elastic modulus E r
[0086] The indentation hardness H of the second layer in this embodiment IT (MPa) relative to the composite elastic modulus E r (GPa) ratio (indentation hardness H IT / Complex elastic modulus E r ) is, for example, greater than 30, or may be greater than 40. On the other hand, for example, less than 85, or may be less than 70. IT / Complex elastic modulus E r If the H value is greater than the above value, the bending resistance tends to be good. It should be noted that in the case of a high-hardness material such as glass with a composite elastic modulus of about 70 GPa, IT When / Er is high, brittle fracture tends to occur easily. However, in the region where the complex elastic modulus is several GPa or less, if H IT When / Er is the above value or more, the bending resistance tends to be good.
[0087] It should be noted that the indentation hardness H IT It can be calculated as follows: Analyze the load-displacement curve prepared above and change the maximum indentation load P max (N) divided by the contact projection area A between the pressure head and the membrane at this time p (mm 2 ), and the obtained value is calculated (the following formula (2)). Indentation hardness H IT It is the arithmetic mean of the values obtained at 10 locations.
[0088] H IT =P max / A p …(2)
[0089] Here, A p This is the contact projection area obtained by correcting the curvature of the indenter tip using the Oliver-Pharr method using a standard sample of fused quartz (5-0098 manufactured by BRUKER).
[0090] (4) Materials
[0091] The second layer preferably contains a resin. The resin contained in the second layer is not particularly limited as long as the second layer has the above-mentioned recovery rate. In addition, the second layer has a function as a bonding layer for bonding the first layer and the third layer.
[0092] The second layer is preferably a so-called heat seal layer. As the resin that can be used as the heat seal layer, thermoplastic resins can be cited. As thermoplastic resins, acrylic resins, polyacrylic polyols, carbamate resins, vinyl chloride resins, vinyl acetate resins, vinyl chloride-vinyl acetate copolymers, styrene-acrylic acid copolymers, acrylic acid-vinyl acetate copolymers, polyester resins, olefin resins, amide resins, cyanoacrylate resins, epoxy resins, polyimide resins, cellulose resins, polycarbonate resins, polyethylene naphthalate resins, etc. can be cited, and they can be used alone or in combination. It should be noted that carbamate resins also include polyester carbamate resins and polyether carbamate resins.
[0093] Among them, preferred examples of the material capable of achieving the above-mentioned recovery rate of 10% or more include polyester resins, urethane resins, and olefin resins.
[0094] In addition, when the second layer is a heat seal layer, the heat-sensitive adhesive composition forming the heat seal layer may further contain a curing agent. Thus, heat resistance and adhesion can be improved. In addition, by adding a curing agent, the complex elastic modulus of the second layer can be adjusted. As a curing agent, for example, isocyanate curing agents, epoxy curing agents, melamine curing agents, etc. can be cited. The curing agent can be used alone or in combination of two or more. When the heat-sensitive adhesive composition contains a curing agent, the second layer contains a cured product of the heat-sensitive adhesive composition.
[0095] In addition, the second layer can contain additives as needed. As additives, for example, light stabilizers, ultraviolet absorbers, infrared absorbers, antioxidants, plasticizers, coupling agents, defoamers, fillers, inorganic or organic particles for adjusting the refractive index, antistatic agents, colorants such as blue pigments or purple pigments, leveling agents, surfactants, lubricants, various sensitizers, flame retardants, adhesion imparting agents, polymerization inhibitors, surface modifiers, etc. can be cited. These additives can be appropriately selected from commonly used additives for use. The content of the additive can be appropriately set. Among them, in order to improve the adhesion with the third layer, the second layer preferably contains a silane coupling agent with the composition.
[0096] On the other hand, the second layer can also be a so-called adhesive layer. As an adhesive for the second resin layer, as long as it is an adhesive that can obtain an adhesive layer with transparency, there is no particular limitation, and for example OCA (Optical Clear Adhesive) can be used. Specifically, acrylic adhesives, silicone adhesives, urethane adhesives, rubber adhesives, polyvinyl ether adhesives, polyvinyl acetate adhesives, etc. can be cited. When the second layer is an adhesive layer, the glass transition temperature of the adhesive layer is preferably above -15 °, more preferably above -10 °. Here, in this specification, the glass transition temperature refers to a value measured by a method (DMA method) based on the value of the peak of the loss tangent (tan δ). In addition, the loss tangent is determined by the value of the loss modulus / storage modulus. These elastic moduli are measured using a dynamic viscoelasticity measuring device to apply force to the adhesive layer at a certain frequency.
[0097] (5) Others
[0098] The thickness of the second layer is, for example, preferably 1 μm or more, more preferably 1.5 μm or more, and particularly preferably 2.0 μm or more. On the other hand, it is preferably 100 μm or less, more preferably 75 μm or less, and particularly preferably 50 μm or less. Specifically, it is preferably in the range of 1 μm or more and 100 μm or less, more preferably in the range of 1.5 μm or more and 75 μm or less, and particularly preferably in the range of 2.0 μm or more and 50 μm or less. If the thickness of the second layer is too thick, the bending resistance may be impaired. On the other hand, if the thickness of the second layer is too thin, it may be impossible to ensure adhesion and peel off.
[0099] In addition, when the second layer is a heat seal layer, it is preferably 1 μm or more, more preferably 1.5 μm or more, and particularly preferably 2.0 μm or more. On the other hand, it is preferably 100 μm or less, more preferably 50 μm or less, more preferably 25 μm or less, and particularly preferably 20 μm or less. Specifically, it is preferably 1 μm or more and 100 μm or less, more preferably 1.0 μm or more and 25 μm or less, and particularly preferably 2.0 μm or more and 20 μm or less.
[0100] In addition, when the second layer is an adhesive layer, it is preferably 30 μm or more, and more preferably 50 μm or more. When the second layer is an adhesive layer, if the thickness of the second layer is too thin, the bending resistance may be impaired. On the other hand, it is preferably 100 μm or less, and more preferably 75 μm or less. Specifically, it is preferably in the range of 30 μm or more and 100 μm or less, and more preferably in the range of 50 μm or more and 75 μm or less.
[0101] Here, the thickness of the second layer can be the average value of the thickness of any 10 locations measured from a cross section in the thickness direction of the laminate observed by a transmission electron microscope (TEM), a scanning electron microscope (SEM) or a scanning transmission electron microscope (STEM). It should be noted that, unless otherwise specified, the method for measuring the thickness of other layers of the laminate can also be set in the same manner.
[0102] The second layer preferably has transparency. Specifically, the total light transmittance of the second layer is preferably 85% or more, more preferably 88% or more, and even more preferably 90% or more.
[0103] Here, the total light transmittance of the second layer can be measured in accordance with JIS K7361-1, for example, using a haze meter HM150 manufactured by Murakami Color Research Laboratory. The total light transmittance of other layers can be measured in the same manner.
[0104] like Figure 3 and Figure 4 As shown, the third layer 3 usually has a first main surface on the second layer side, a second main surface facing the first main surface, and a side surface SS different from the first main surface S1 and the second main surface S2. In this embodiment, the second layer 2 preferably covers the side surface SS of the third layer 3. In this case, the width W2 of the second layer 2 is greater than the width W3 of the third layer 3.
[0105] Here, the case where the third layer is a glass substrate is described. Microcracks are easily generated in the glass substrate during processing, and microcracks are easily generated at the ends of the glass substrate during the cutting process of the glass substrate. If microcracks exist in the glass substrate, it is easy to cause ruptures starting from the microcracks. In addition, if chemically strengthened glass is used as the glass substrate, the impact resistance and bending resistance can be improved. However, in this case, when the glass substrate composed of chemically strengthened glass is cut, the compressive stress layer formed on the surface of the chemically strengthened glass does not exist on the cut surface of the glass substrate, that is, the side surface, so the side strength of the glass substrate is also reduced.
[0106] When the third layer is a glass substrate, the strength of the side surface of the glass substrate can be improved by covering the side surface of the third layer with the second layer. In addition, the microcracks on the side surface of the glass substrate can be filled with the second layer, thereby improving the strength of the side surface of the glass substrate. Thus, the impact resistance of the end of the glass laminate can be improved.
[0107] The degree of covering of the side surface of the third layer by the second layer is not particularly limited as long as the strength of the side surface of the third layer can be improved by covering the side surface of the third layer with the second layer. For example, the entire side surface of the third layer may be covered by the second layer, or only a portion of the side surface of the third layer may be covered by the second layer. Specifically, Figure 3 As shown, the thickness direction D of the side SS T All of the second layer 2 is covered, or Figure 4 As shown, the thickness direction D of the side SS T A portion of is covered by the second layer 2.
[0108] As the thickness direction D T The degree of coverage of the side of the third layer by the second layer on the glass substrate, specifically, the ratio (Tc2 / T3) of the thickness Tc2 of the side of the third layer covered by the second layer to the thickness T3 of the third layer is, for example, greater than 0.5, greater than 0.6, or greater than 0.7. On the other hand, it is, for example, less than 1.0, less than 0.9, or less than 0.8. Specifically, the above ratio (Tc2 / T3) is, for example, greater than 0.5 and less than 1.0, greater than 0.6 and less than 0.9, or greater than 0.7 and less than 0.8. By being within the above ratio range, the impact resistance of the side of the glass substrate becomes good.
[0109] The shape of the glass substrate is usually a rectangular parallelepiped, which is a hexahedron. In addition, for example, when the glass substrate is chamfered, the shape of the glass substrate is also usually a rectangular parallelepiped, which can be regarded as a roughly hexahedron. In this case, the glass substrate has a first face and a second face facing each other and four side faces. In this case, as the degree of coverage of the side face of the glass substrate by the second layer, at least one of the four side faces of the glass substrate is covered by the second layer. That is, in this case, one of the four side faces of the glass substrate may be covered by the second layer, two side faces may be covered by the second layer, three side faces may be covered by the second layer, or four side faces may be covered by the second layer.
[0110] Among them, it is preferred that two of the four side surfaces of the glass substrate that face each other are covered with the second layer, and it is preferred that two of the four side surfaces of the glass substrate that are substantially parallel to the bending direction of the glass laminate are covered with the second layer. This is because it is possible to suppress the generation of cracks at the bent portion when the glass laminate is bent, thereby improving the bending resistance.
[0111] 2. Layer 1
[0112] The first layer usually contains a resin. In addition, the first layer has light transmittance, and when the laminate in the present embodiment is arranged on the observer side of the display panel of the display device, it is arranged at a position closer to the observer side than the third layer described later. The first layer can also function as an impact-absorbing layer with impact absorption. For example, when the third layer is a glass substrate, it can also function as an anti-scattering layer that suppresses the scattering of glass when the glass substrate is broken. For example, when the third layer is a glass substrate, by configuring the first layer on the glass substrate, when an impact is applied to the laminate, the first layer absorbs the impact, which can suppress the rupture of the glass substrate and improve the impact resistance. Furthermore, through the first layer, even if the glass substrate is damaged, the scattering of the glass can be suppressed.
[0113] The first layer has transparency. Specifically, the total light transmittance of the first resin layer is preferably 85% or more, more preferably 88% or more, and even more preferably 90% or more.
[0114] The complex elastic modulus of the first layer is, for example, 6.0 GPa or more, preferably 6.5 GPa or more. By making the complex elastic modulus of the first layer within the above range, the first layer can be used to improve impact resistance and damage resistance. As the resin contained in such a first layer, the resin described later can be cited. On the other hand, the complex elastic modulus of the first layer is, for example, preferably 70 GPa or less, preferably 10 GPa or less. Specifically, the complex elastic modulus of the first layer is, for example, preferably 6.0 GPa or more and 70 GPa or less, more preferably 6.5 GPa or more and 10 GPa or less. The method for measuring the complex elastic modulus of the first layer can be the same as the method for measuring the complex elastic modulus of the second layer mentioned above.
[0115] (a) Resin
[0116] As the resin contained in the first layer, specifically, polyester resin, polyimide resin, cellulose resin, cycloolefin polymer (COP), epoxy resin, polyurethane, acrylic resin, cycloolefin (COP), polycarbonate (PC) etc. can be cited. This is because a resin layer with transparency and impact absorption can be obtained. These resins can be used alone or in combination of two or more.
[0117] As polyester resins, for example, polyethylene terephthalate (PET), polytrimethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate (PEN), etc. can be cited. Polyimide resins refer to polymers having an imide bond in the main chain. As polyimide resins, for example, polyimide, polyamide-imide, polyesterimide, polyetherimide, etc. can be cited. As cellulose resins, for example, triacetyl cellulose (TAC), etc. can be cited. As acrylic resins, for example, polymethyl (meth)acrylate, polyethyl (meth)acrylate, etc. can be cited. Among them, polyimide resins are preferred from the aspects of having bending resistance, excellent hardness and transparency.
[0118] The first layer is preferably a resin film containing a resin selected from the above-mentioned resin group.
[0119] (b) Additives
[0120] The first layer may further contain additives as required, such as ultraviolet absorbers, light stabilizers, antioxidants, inorganic particles, silica fillers for smooth winding, surfactants for improving film forming properties and degassing properties, and adhesion improvers.
[0121] When the first layer contains an ultraviolet absorber, degradation of the first layer due to ultraviolet rays can be suppressed. Among them, when the first layer contains polyimide, the color change of the resin layer containing polyimide over time can be suppressed. In addition, in a display device including a laminate, degradation of components arranged closer to the display panel side than the laminate, such as a polarizing element, due to ultraviolet rays can be suppressed.
[0122] Examples of the ultraviolet absorber contained in the first layer include triazine ultraviolet absorbers, benzophenone ultraviolet absorbers such as hydroxybenzophenone ultraviolet absorbers, and benzotriazole ultraviolet absorbers.
[0123] In addition, the ultraviolet absorber is preferably a polymer or an oligomer. This is because it is possible to suppress the exudation of the ultraviolet absorber when the laminate is repeatedly bent. As such an ultraviolet absorber, for example, a polymer or an oligomer having a triazine skeleton, a benzophenone skeleton or a benzotriazole skeleton can be cited, specifically, a substance obtained by thermally copolymerizing a (meth)acrylate having a benzotriazole skeleton or a benzophenone skeleton with methyl methacrylate (MMA) in an arbitrary ratio.
[0124] The content of the ultraviolet light absorber in the first layer is not particularly limited, and is, for example, preferably 1% by mass or more and 6% by mass or less, and more preferably 2% by mass or more and 5% by mass or less. If the content of the ultraviolet light absorber is too little, the effect brought by the ultraviolet light absorber cannot be fully obtained sometimes. In addition, if the content of the ultraviolet light absorber is too much, the resin layer may be significantly colored, or the strength of the resin layer may be reduced.
[0125] 3. Layer 3
[0126] The third layer is not particularly limited as long as it has transparency, and examples thereof include a glass substrate and a resin substrate. In the present embodiment, a glass substrate is preferred.
[0127] (1) Glass substrate
[0128] The glass constituting the glass substrate is not particularly limited as long as it has transparency, and examples thereof include silicate glass and silica glass. Among them, borosilicate glass, aluminosilicate glass, and aluminoborosilicate glass are preferred, and alkali-free glass is more preferred. Commercially available products of the glass substrate include, for example, the ultra-thin plate glass G-Leaf of Nippon Electric Glass Co., Ltd. and the ultra-thin film glass of Matsunami Glass Industries Co., Ltd.
[0129] In addition, the glass constituting the glass substrate is also preferably chemically strengthened glass. Chemically strengthened glass is preferred in terms of excellent mechanical strength and the ability to be thinned accordingly. Typically, chemically strengthened glass is glass whose mechanical properties are strengthened by chemical methods by replacing sodium with potassium or other partially exchanged ion species near the surface of the glass, and has a compressive stress layer on the surface.
[0130] Examples of the glass constituting the chemically strengthened glass substrate include aluminosilicate glass, soda-lime glass, borosilicate glass, lead glass, alkali barium glass, and aluminoborosilicate glass.
[0131] Examples of commercially available chemically strengthened glass substrates include Gorilla Glass from Corning, Dragontrail from AGC, and chemically strengthened glass from Schott.
[0132] The thickness of the glass substrate is, for example, preferably 115 μm or less, more preferably 110 μm or less. On the other hand, it is more preferably 15 μm or more, more preferably 20 μm or more, and particularly preferably 25 μm or more. The thickness of the glass substrate in this embodiment is preferably in the range of 15 μm or more and 115 μm or less, more preferably in the range of 20 μm or more and 110 μm or less.
[0133] By setting the thickness of the glass substrate within the above range, good flexibility can be obtained, and sufficient hardness can be obtained. In addition, curling of the display device laminate can be suppressed. Furthermore, it is preferable in terms of weight reduction of the display device laminate.
[0134] (2) Resin substrate
[0135] The resin constituting the resin substrate is not particularly limited as long as a transparent resin substrate can be obtained.
[0136] The composite elastic modulus of the resin substrate is, for example, 6.0 GPa or more, preferably 6.5 GPa or more. On the other hand, the composite elastic modulus of the resin substrate is, for example, 70 GPa or less, preferably 10 GPa or less. Specifically, the composite elastic modulus of the resin substrate is, for example, preferably 6.0 GPa or more and 70 GPa or less, more preferably 6.5 GPa or more and 10 GPa or less. The determination method of the composite elastic modulus of the resin substrate can be the same as the determination method of the composite elastic modulus of the second layer.
[0137] As the resin contained in the resin substrate, for example, polyimide resin, polyamide resin, polyester resin, etc. can be cited. As the polyimide resin, for example, polyimide, polyamide-imide, polyetherimide, polyesterimide, etc. can be cited. As the polyester resin, for example, polyethylene terephthalate, polytrimethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, etc. can be cited. Among them, from the aspects of having bending resistance, excellent hardness and transparency, polyimide resin, polyamide resin or a mixture thereof is preferred, and polyimide resin is more preferred.
[0138] The polyimide resin is not particularly limited as long as a transparent resin substrate can be obtained, and polyimide and polyamide-imide are preferably used among the above-mentioned ones. They can improve flexibility and bending resistance, and have a relatively high refractive index, so the reflectivity can be easily adjusted.
[0139] The thickness of the resin substrate is preferably, for example, 10 μm to 100 μm, more preferably 20 μm to 80 μm. By making the thickness of the resin substrate within the above range, good flexibility can be obtained, and sufficient hardness can be obtained. In addition, the curling of the display device laminate can also be suppressed. Furthermore, it is preferred in terms of lightweighting of the display device laminate.
[0140] 4. Other layers
[0141] The laminate in the present embodiment can also have other layers in addition to the above-mentioned first layer, second layer and third layer. The display device component in the present embodiment can further have a functional layer on the surface side opposite to the third layer of the first layer, between the first layer and the second layer. As the functional layer configured on the surface side opposite to the third layer of the first layer, for example, a hard coat layer, a protective layer, an anti-reflection layer, an anti-glare layer, etc. can be cited. As the functional layer configured between the first layer and the second layer, a decorative layer and a primer layer can be cited.
[0142] The functional layer may be a single layer or may have multiple layers. In addition, the functional layer may be a layer having a single function or may have multiple layers having different functions. For example, the laminate in the present embodiment may have a hard coating layer and a protective layer in sequence from the first layer side as the functional layer disposed on the first layer and on the opposite side of the third layer.
[0143] (1) Hard coating
[0144] For example Figure 2 As shown, the laminate in this embodiment preferably further has a hard coating layer 5 on the surface of the first layer 1 opposite to the third layer 3. The hard coating layer is a member for increasing the surface hardness. By providing the hard coating layer, the scratch resistance can be improved.
[0145] (a) Characteristics of hard coating
[0146] Here, the "hard coating layer" is a component for improving the surface hardness. Specifically, it refers to a component that shows a hardness of "H" or above when performing a pencil hardness test specified in JIS K 5600-5-4 (1999) in the display device component of this embodiment having a hard coating layer.
[0147] When the laminate in the present embodiment has a hard coat layer on the surface of the first layer opposite to the third layer, the pencil hardness of the surface of the laminate on the hard coat layer side is preferably H or higher, more preferably 2H or higher, and further preferably 3H or higher.
[0148] Here, the pencil hardness is measured by the pencil hardness test specified in JIS K5600-5-4 (1999). Specifically, it can be carried out by using a test pencil specified in JIS-S-6006 to perform a pencil hardness test specified in JIS K5600-5-4 (1999) on the surface of the hard coating side of the display device component, and evaluating the highest pencil hardness without damage. As measurement conditions, it can be set to an angle of 45°, a load of 750g, a speed of 0.5mm / second or more and 1mm / second or less, and a temperature of 23±2°C. As a pencil hardness tester, for example, a pencil scratch coating hardness tester manufactured by Toyo Seiki Co., Ltd. can be used.
[0149] (b) Composition of hard coating layer
[0150] The hard coating layer may be a single layer or may have a multilayer structure of more than two layers. When the hard coating layer has a multilayer structure, in order to improve the surface hardness and to balance the bending resistance and the elastic modulus, the hard coating layer preferably has a layer for satisfying the pencil hardness and a layer for satisfying the dynamic bending test (a layer for satisfying the scratch resistance).
[0151] (c) Hard coating material
[0152] As the material of the hard coat layer, for example, an organic material, an inorganic material, an organic-inorganic composite material, or the like can be used.
[0153] Wherein, the material of hard coat is preferably organic material. Specifically, hard coat preferably comprises the cured product of the resin composition containing polymerizable compound. The cured product of the resin composition containing polymerizable compound can be obtained by using polymerization initiator as needed and polymerizing the polymerizable compound by known method.
[0154] (i) Polymerizable compounds
[0155] The polymerizable compound has at least one polymerizable functional group in the molecule. As the polymerizable compound, for example, at least one of a radical polymerizable compound and a cation polymerizable compound can be used.
[0156] A free radical polymerizable compound refers to a compound having a free radical polymerizable group. The free radical polymerizable group possessed by the free radical polymerizable compound is not particularly limited as long as it is a functional group capable of undergoing free radical polymerization reaction, and examples thereof include groups containing carbon-carbon unsaturated double bonds, and specifically, vinyl, (meth) acryloyl, etc. It should be noted that when the free radical polymerizable compound has two or more free radical polymerizable groups, these free radical polymerizable groups may be the same or different.
[0157] From the viewpoint of increasing the hardness of the hard coat layer, the number of radically polymerizable groups contained in one molecule of the radically polymerizable compound is preferably 2 or more, more preferably 3 or more.
[0158] Cationic polymerizable compounds refer to compounds having cationic polymerizable groups. As the cationic polymerizable groups possessed by the cationic polymerizable compounds, as long as they are functional groups capable of cationic polymerization, there is no particular limitation, and examples thereof include epoxy groups, oxetane groups, vinyl ether groups, etc. It should be noted that when the cationic polymerizable compounds have two or more cationic polymerizable groups, these cationic polymerizable groups may be the same or different.
[0159] From the viewpoint of increasing the hardness of the hard coat layer, the number of cationically polymerizable groups contained in one molecule of the cationically polymerizable compound is preferably 2 or more, more preferably 3 or more.
[0160] In addition, as a cationic polymerizable compound, a compound having at least one of an epoxy group and an oxetane group as a cationic polymerizable group is preferred, and a compound having at least one of two epoxy groups and an oxetane group in one molecule is more preferred. From the aspect of the small shrinkage associated with the polymerization reaction, cyclic ether groups such as epoxy groups and oxetane groups are preferred. In addition, compounds having epoxy groups in cyclic ether groups have the following advantages: it is easy to obtain compounds with diverse structures, it will not adversely affect the durability of the obtained hard coating, and the compatibility with free radical polymerizable compounds is also easy to control. In addition, the oxetane group in the cyclic ether group has the following advantages: compared with epoxy groups, the polymerization degree is high and the toxicity is low. When the obtained hard coating is combined with a compound having an epoxy group, the speed of forming a network structure obtained by the cationic polymerizable compound in the coating film can be accelerated. Even in the area mixed with the free radical polymerizable compound, unreacted monomers will not remain in the film, and an independent network structure can be formed.
[0161] (ii) Polymerization initiator
[0162] Resin combination can also contain polymerization initiator as required. As polymerization initiator, free radical polymerization initiator, cationic polymerization initiator, free radical and cationic polymerization initiator etc. can be appropriately selected for use. These polymerization initiators are decomposed by at least one of light irradiation and heating, and free radical or cation is produced to make free radical polymerization and cationic polymerization proceed. It should be noted that, in hard coat, polymerization initiator is sometimes completely decomposed and does not remain.
[0163] Specific examples of radical polymerization initiators and cationic polymerization initiators include those described in JP-A-2018-104682.
[0164] (iii) Particles
[0165] The hard coat layer preferably contains inorganic or organic particles, and more preferably contains inorganic fine particles. By making the hard coat layer contain particles, the hardness can be increased.
[0166] As inorganic particles, for example, metal oxide particles such as silicon dioxide (SiO2), aluminum oxide, zirconium oxide, titanium dioxide, zinc oxide, germanium oxide, indium oxide, tin oxide, indium tin oxide (ITO), antimony oxide, cerium oxide, metal fluoride particles such as magnesium fluoride and sodium fluoride, metal particles, metal sulfide particles, metal nitride particles, etc. can be cited. Among them, metal oxide particles are preferred, and at least one selected from silicon dioxide particles and aluminum oxide particles is more preferred, and silicon dioxide particles are further preferred. This is because excellent hardness can be obtained.
[0167] The hardness of the hard coat layer can be controlled by adjusting the size and content of the inorganic particles. For example, the content of the silica particles is preferably 25 parts by mass or more and 60 parts by mass or less based on 100 parts by mass of the polymerizable compound.
[0168] (iv) UV absorber
[0169] The hard coat layer may also contain an ultraviolet absorber. It is possible to suppress the degradation of the first layer due to ultraviolet rays. In particular, when the first layer contains polyimide, the color change of the first layer containing polyimide over time can be suppressed. In addition, in a display device having a display device component, it is possible to suppress the degradation of components such as polarizing elements disposed closer to the display panel side than the display device component due to ultraviolet rays.
[0170] The ultraviolet absorber contained in the hard coating layer preferably has a peak absorption wavelength in the absorbance measurement of 300 nm to 390 nm, more preferably 320 nm to 370 nm, and further preferably 330 nm to 370 nm. This is because such an ultraviolet absorber can efficiently absorb ultraviolet rays in the UVA region, and on the other hand, by staggering the peak wavelength with the absorption wavelength of 250 nm of the initiator used to cure the hard coating layer, the curing of the hard coating layer will not be inhibited, and a hard coating layer with ultraviolet absorption ability can be formed.
[0171] The ultraviolet absorber preferably has a peak absorption wavelength of 380 nm or less from the viewpoint of suppressing coloration caused by the ultraviolet absorber.
[0172] The absorbance of the ultraviolet absorber can be measured, for example, using an ultraviolet-visible-near-infrared spectrophotometer (for example, JASCO Corporation V-7100).
[0173] The ultraviolet absorber may be the same as the ultraviolet absorber used in the first layer.
[0174] Among them, from the aspect of suppressing the degradation of the above-mentioned first layer due to ultraviolet rays, at least one ultraviolet absorber selected from the group consisting of hydroxybenzophenone ultraviolet absorbers and benzotriazole ultraviolet absorbers is preferred, and at least one ultraviolet absorber selected from the group consisting of hydroxybenzophenone ultraviolet absorbers is more preferred.
[0175] The content of the ultraviolet absorber in the hard coat layer is preferably 10% by mass or less, and more preferably 7% by mass or less, from the perspective of suppressing haze by mixing the ultraviolet absorber. In addition, from the perspective of suppressing degradation of the first layer due to ultraviolet rays and improving durability, the content of the ultraviolet absorber in the hard coat layer is preferably 1% by mass or more and 6% by mass or less, and more preferably 2% by mass or more and 5% by mass or less.
[0176] (v) Antifouling agent
[0177] The hard coat layer may contain an antifouling agent, which can impart antifouling properties to the display device member.
[0178] The antifouling agent is not particularly limited, and examples thereof include silicone antifouling agents, fluorine antifouling agents, and silicone and fluorine antifouling agents. In addition, the antifouling agent may also be an acrylic antifouling agent. The antifouling agent may be used alone or in combination of two or more.
[0179] The hard coating layer containing silicone antifouling agents and fluorine antifouling agents is not easy to be attached with fingerprints (not easy to be conspicuous) and has good wiping properties. In addition, when silicone antifouling agents and fluorine antifouling agents are contained, the surface tension when applying the curable resin composition for hard coating can be reduced, so the leveling property is good, and the appearance of the obtained hard coating layer becomes good.
[0180] In addition, the hard coating layer containing the silicone antifouling agent has good sliding properties and good scratch resistance. A display device having a display device component having such a hard coating layer containing the silicone antifouling agent has good sliding properties when touched with a finger or a pen, and thus has good touch.
[0181] The content of the antifouling agent is, for example, preferably 0.01 parts by mass to 3.0 parts by mass relative to 100 parts by mass of the resin component. If the content of the antifouling agent is too small, sufficient antifouling properties may not be imparted to the hard coat layer. If the content of the antifouling agent is too large, the hardness of the hard coat layer may be reduced.
[0182] (vi) Other additives
[0183] The hard coat layer may further contain additives as required. The additives are appropriately selected according to the functions imparted to the hard coat layer, and are not particularly limited, and include, for example, inorganic or organic particles for adjusting the refractive index, infrared absorbers, anti-glare agents, antifouling agents, antistatic agents, colorants such as blue pigments or purple pigments, leveling agents, surfactants, lubricants, various sensitizers, flame retardants, adhesion imparting agents, polymerization inhibitors, antioxidants, light stabilizers, surface modifiers, etc.
[0184] (d) Thickness of hard coating
[0185] The thickness of the hard coat layer can be appropriately selected according to the material of the hard coat layer, the function of the hard coat layer and the purpose of the laminate. For example, when the material of the hard coat layer is an organic material, the thickness of the hard coat layer is preferably 2 μm to 50 μm, more preferably 3 μm to 30 μm, further preferably 5 μm to 20 μm, and particularly preferably 6 μm to 10 μm. In addition, for example, when the material of the hard coat layer is an inorganic material, the thickness of the hard coat layer can be about tens of nanometers. If the thickness of the hard coat layer is within the above range, sufficient hardness can be obtained as a hard coat layer, and a display device component with good bending resistance can be obtained.
[0186] (e) Method for forming hard coating layer
[0187] The method for forming the hard coat layer is appropriately selected depending on the material of the hard coat layer, and examples thereof include a method of applying a hard coat curable resin composition containing the polymerizable compound on the first layer and curing it, or a vapor deposition method, a sputtering method, and the like.
[0188] The curable resin composition for hard coat layer contains a polymerizable compound, and may further contain a polymerization initiator, particles, an ultraviolet absorber, a solvent, additives, and the like as necessary.
[0189] As a method for coating the curable resin composition for hard coating on the first layer, there is no particular limitation as long as it is a method that can be coated with a target thickness, and general coating methods such as gravure coating, reverse gravure coating, gravure offset coating, spin coating, roll coating, reverse roll coating, blade coating, dip coating, screen printing, etc. can be cited. In addition, a transfer method can also be used as a method for forming a coating film of the resin composition for hard coating.
[0190] The coating of the curable resin composition for hard coating is dried as needed to remove the solvent. As the drying method, for example, reduced pressure drying or heating drying, and a method of combining these drying methods can be cited. For example, drying can be performed by heating at a temperature of 30° C. to 120° C. for 10 seconds to 180 seconds.
[0191] The method for curing the coating film of the curable resin composition for a hard coat layer is appropriately selected according to the polymerizable group of the polymerizable compound, and for example, at least one of light irradiation and heating can be used.
[0192] (2) Protective layer
[0193] The laminate in the present embodiment may further include a protective layer on the surface of the first layer opposite to the second layer.
[0194] The protective layer has transparency. Specifically, the total light transmittance of the protective layer is preferably 85% or more, more preferably 88% or more, and even more preferably 90% or more.
[0195] The protective layer is not particularly limited as long as it has transparency, and may contain, for example, a resin. The resin used in the protective layer is not particularly limited as long as it can provide a transparent protective layer, and a general resin can be used.
[0196] Examples of a method for disposing a protective layer on one surface of the first layer include a method of using a protective film as the protective layer and bonding the first layer and the protective film via an adhesive layer; a method of forming the protective layer on the first layer; and the like.
[0197] (3) Primer
[0198] like Figure 5 As shown in (a), the laminate 10A in this embodiment may have a primer layer 6 between the first layer 1 and the second layer 2. The material of the primer layer is not particularly limited as long as it is a material that can improve the adhesion between the first layer 1 and the second layer 2, and resins can be cited, for example. As resins, for example, (meth) acrylic resins, urethane resins, (meth) acrylic acid urethane copolymers, vinyl chloride-vinyl acetate copolymer resins, polyesters, butyral resins, chlorinated polypropylene, chlorinated polyethylene, epoxy resins, silicone resins, etc. can be cited. These resins can be used alone or in combination of two or more.
[0199] The thickness of the primer layer may be any thickness as long as it can improve the adhesion between the first layer and the second layer, and may be, for example, 0.1 μm to 10 μm, and preferably 0.2 μm to 5 μm.
[0200] As the formation method of the primer layer, for example, a method of applying a primer composition on the first layer can be mentioned. As the coating method, for example, a general coating method such as a gravure coating method, a reverse gravure coating method, a gravure offset coating method, a spin coating method, a roll coating method, a reverse roll coating method, a blade coating method, a dip coating method, a screen printing method, a die coating method can be mentioned. In addition, a transfer method can also be used as the formation method of the primer layer.
[0201] (4) Decorative layer
[0202] like Figure 5 As shown in (b) of FIG. 1 , the laminate 10A in this embodiment may include a decorative layer 7 between the first layer 1 and the second layer 2. Figure 5 As shown in (c) of FIG. 1 , the laminate 10A in the present embodiment may include a decorative layer 7 and a primer layer 6. In this case, the decorative layer 7 may be disposed between the primer layer 6 and the second layer.
[0203] The decorative layer includes a colorant and a binder resin. The binder resin included in the decorative layer is not particularly limited, and a resin generally used in a decorative layer can be used. In addition, the colorant included in the decorative layer is not particularly limited, and a known colorant generally used in a decorative layer can be used.
[0204] The decorative layer is usually disposed on a portion of the first layer. The decorative layer may have a pattern shape. The thickness of the decorative layer is not particularly limited, and may be, for example, 5 μm or more and 40 μm or less.
[0205] 5. Characteristics of laminates
[0206] (1) Total light transmittance and haze
[0207] The total light transmittance of the laminate in the present embodiment is, for example, preferably 80% or more, more preferably 85% or more, and even more preferably 88% or more. By making the total light transmittance so high, a laminate having good transparency can be obtained.
[0208] The haze of the laminate in the present embodiment is, for example, preferably 2.0% or less, more preferably 1.5% or less, and further preferably 1.0% or less. By making the haze so low, a laminate having good transparency can be obtained.
[0209] Here, the haze of the laminate can be measured in accordance with JIS K-7136, for example, using a haze meter HM150 manufactured by Murakami Color Research Laboratory.
[0210] (2) Bending resistance
[0211] The laminate in the present embodiment preferably has bending resistance. In particular, when the third layer of the laminate in the present embodiment is a glass substrate having a thickness of 30 μm, the second layer preferably does not peel off when a clamshell bending test is repeated 200,000 times, wherein the laminate is folded from a flat state so that the curvature radius of the bent portion is 1.5 mm and then opened again to a flat state.
[0212] It is particularly preferred that the second layer does not peel off when the action of folding the stack from a flat state with a curvature radius of 1.25 mm at the bent portion and then opening it again to become flat is repeated 200,000 times as one cycle.
[0213] Furthermore, when the thickness of the glass substrate is 100 μm, it is preferred that the second layer not be peeled off when the test is performed with the curvature radius of the curved portion being set to 4 mm.
[0214] According to the clamshell bending test, deformation occurs only in a partial region of the laminate located between two plates described later. Therefore, the bending resistance of the laminate when a local bent portion occurs can be evaluated.
[0215] (Clamshell bend test)
[0216] The clamshell bending test is performed as follows using, for example, a small tabletop endurance test system Tension-Free (registered trademark) Folding Clamshell-type (manufactured by Yuasa System Co., Ltd.). In the small tabletop endurance test system, the laminate is held by two plates of a double-jointed clamshell type. For the two plates, if one plate is moved by a rotating reciprocating drive shaft, the parallel connecting rods are used to open and close while maintaining the same angle with each other.
[0217] First, prepare a test piece of the laminate with a size of 20 mm × 100 mm. Fig.15 (a) and Fig.15 As shown in (b), the sample of the laminate 10 is fixed flatly on two plates 101A and 101B located on the same plane. It should be noted that Fig.15 (b) is Fig.15 Then, as Fig.15 As shown in (c), the two plates 101A and 101B are rotated symmetrically relative to the plane X, and the two plates are made parallel to each other while being spaced a certain distance apart. As a result, the laminate is folded between the two plates at a predetermined radius of curvature R. Next, the two plates are returned to their original state, so that the laminate is located on the same plane, and the laminate becomes flat in the initial state, thereby completing a cycle. When the two plates are isolated and parallel, the interval between the two plates is d1, and d1 / 2 is substantially equivalent to the radius of curvature R.
[0218] In the clamshell bending test, the laminate may be folded so that the first layer of the laminate is on the inside, or the laminate may be folded so that the third layer of the laminate is on the inside, but it is preferred that the above-mentioned bending resistance be present in either case. In the present embodiment, in particular, when the laminate is folded so that the first layer of the laminate is on the inside, it is preferred that the above-mentioned bending resistance be present.
[0219] It is preferred that the laminate in the present embodiment does not cause peeling of the second layer in the U-shaped bending test described below.
[0220] In the U-shaped bending test, the laminate may be folded so that the first layer of the laminate becomes the inner side, or the laminate may be folded so that the third layer of the laminate becomes the inner side, but it is preferred that the above-mentioned bending resistance is present in either case. In the present embodiment, in particular, when the laminate is folded so that the first layer of the laminate becomes the inner side, it is preferred that the above-mentioned bending resistance is present.
[0221] (U-shaped bending test)
[0222] The U-shaped bending test was conducted as follows. First, a test piece of the laminate having a size of 20 mm × 100 mm was prepared. Fig.14 As shown in (a), the short side 10P of the laminate 10 and the short side 10Q facing the short side 10P are fixed by the fixing parts 100A and 100B arranged in parallel. Fig.14 As shown in (a), the fixing portion 100B can slide in the horizontal direction. Fig.14 As shown in (b) to (c), the fixing portion 100B is moved close to the fixing portion 100A, so that the laminate 10 is bent into a U-shape, and the laminate 10 is bent 180° so that the interval d2 between the short sides 10P and 10Q facing each other becomes 3.0 mm. This action is repeated 200,000 times.
[0223] (3) Peel strength
[0224] The peel strength of the laminate in the present embodiment is, for example, 5N / 20mm width or more, 6N / 20mm width or more, or 10N / 20mm width or more. If the peel strength is above the above value, the adhesive force of the second layer is sufficient, and the laminate in which the first layer and the third layer are fully bonded is formed. That is, the peel strength between the first layer and the second layer of the laminate in the present embodiment and the peel strength between the second layer and the third layer are preferably within the above range. On the other hand, the peel strength of the laminate is, for example, 50N / 20mm width or less, or 40N / 20mm width or less.
[0225] Here, the method for measuring the peel strength of the laminate in the present embodiment is as follows.
[0226] The peel strength can be measured by a 180-degree peel test according to JIS Z0237:2009. First, a test piece with a width of 20 mm and a length of 100 mm is cut out from the laminate. As a universal testing machine (tensile testing machine), "Autograph AG-X 1N (load sensor: SBL-1KN)" manufactured by Shimadzu Corporation is used. By a 180-degree peel test according to JIS Z0237:2009, peeling is performed at the interface between the first layer and the third layer under the conditions of a temperature of 25°C, a distance between the chucks of the tensile testing machine of 50 mm, a tensile speed of 300 mm / min, and a peeling angle of 180 degrees, and the peel strength is measured.
[0227] In addition, when the width of the test piece is not 20 mm, the peel strength (actually measured value) measured by the above-mentioned 180 degree peel test is converted into 20 mm width by the following formula.
[0228] Peel strength converted to 20 mm width [N / 20 mm] = measured value of peel strength [N / 20 mm] × 20 [mm] / width of test piece [mm]
[0229] 6. Application of laminate
[0230] The laminate in this embodiment can be used as a material disposed on the observer side of the display panel, i.e., a front panel, in a display device. The laminate in this embodiment can be used, for example, in display devices used in electronic devices such as smartphones, tablet terminals, wearable terminals, personal computers, televisions, digital signage, public information displays (PIDs), and vehicle-mounted displays.
[0231] Among them, the laminate in this embodiment can be preferably used for flexible displays such as foldable displays, rollable displays, and bendable displays, and can be particularly preferably used for foldable displays.
[0232] When the laminate in this embodiment is arranged on the surface of a display device, it can be arranged in a manner that the surface on the third layer side becomes the display panel side and the surface on the first layer side becomes the outer side, or it can be arranged in a manner that the surface on the first layer side becomes the display panel side and the surface on the third layer side becomes the outer side. The former is preferred.
[0233] The method of placing the laminate in the present embodiment on the surface of the display device is not particularly limited, and examples thereof include a method using an adhesive layer, etc. As the adhesive layer, a known adhesive layer used for bonding laminates in display devices can be used.
[0234] The laminate in the present embodiment includes a first layer, a second layer, and a third layer in this order, and the recovery rate of the cross section of the second layer by the nanoindentation method is equal to or greater than a predetermined value.
[0235] A-2. Laminated body (Second embodiment)
[0236] Figure 6 Schematic cross-sectional view showing an example of a laminate according to the second embodiment of the present disclosure. Figure 6 As shown, the laminate 10B in this embodiment has a thickness direction D T The first layer 1, the second layer 2, the fourth layer 4, and the third layer 3 are sequentially provided thereon. In the present disclosure, the recovery rate of each cross section of the second layer 2 and the fourth layer 4 by the nanoindentation method is equal to or greater than a predetermined value.
[0237] As described above, for example, in the case of a foldable display, when a laminate having a first layer, a second layer, a fourth layer, and a third layer is repeatedly bent with a localized bent portion, there is a problem that the second layer peels off from the first layer or the third layer peels off from the fourth layer. Regarding this phenomenon, it is believed that the harder the layer (for example, a layer with a high complex elastic modulus), the higher the shear stress concentrated on the bent portion, and therefore the more likely it is to peel off.
[0238] However, the inventors of the present disclosure have found that the ease with which the second layer and the fourth layer peel off does not depend on the complex elastic modulus. In addition, the inventors of the present disclosure have conducted in-depth research and, for the same reasons as above, have found that by making the recovery rate of each cross section of the second layer and the fourth layer based on the nanoindentation method greater than a specified value, even when the bending portion is local, the peeling of the second layer and the peeling of the fourth layer can be suppressed, and the bending resistance becomes good.
[0239] Furthermore, it was found that according to the present embodiment, by disposing the fourth layer between the third layer and the second layer, excellent impact resistance was achieved.
[0240] 1. Layer 2
[0241] The second layer in this embodiment is disposed between the first layer and the third layer and functions as a bonding layer that bonds the first layer to the third layer together with the fourth layer. In this embodiment, the recovery rate of the cross section in the thickness direction of the second layer by nanoindentation is greater than a predetermined value.
[0242] Other features of the second layer are the same as those of the second layer in the first embodiment.
[0243] 2. Layer 4
[0244] The fourth layer in this embodiment is arranged between the first layer and the third layer, and has a function as a bonding layer that bonds the first layer to the third layer together with the second layer. In addition, it is arranged between the second layer and the third layer, and has a function as an impact absorbing layer. By arranging the fourth layer, when an impact is applied to the laminate, the impact can be absorbed, and the impact resistance can be improved. In addition, when the third layer is a glass substrate, the cracking of the glass substrate can be suppressed.
[0245] In this embodiment, the recovery rate of the cross section of the fourth layer in the thickness direction by the nanoindentation method is greater than a predetermined value. T The cross section is obtained by cutting (in the stacking direction of the stack).
[0246] (1) Recovery rate based on nanoindentation method
[0247] The recovery rate of the cross section of the fourth layer based on the nanoindentation method is usually 10% or more, can be 20% or more, can be 30% or more, can be 40% or more, and can be 50% or more. On the other hand, the above recovery rate is, for example, 80% or less, can be 70% or less, and can be 60% or less.
[0248] Specifically, it is preferably in the range of 10% to 80%, more preferably in the range of 20% to 70%, and particularly preferably in the range of 30% to 60%.
[0249] The method for measuring the recovery rate of the cross section of the fourth layer by the nanoindentation method is the same as the method for measuring the recovery rate of the cross section of the second layer by the nanoindentation method in the first embodiment.
[0250] (2) Composite elastic modulus
[0251] The composite elastic modulus of the 4th layer in the present embodiment can be, for example, 0.01 GPa or more, preferably 0.05 GPa or more, and more preferably greater than 0.05 GPa. Furthermore, it is particularly preferably 3.0 GPa or more. If the composite elastic modulus of the 4th layer is above the above value, the impact resistance of the laminate is improved, so it is preferred. In addition, the composite elastic modulus of the 4th layer is, for example, 7.0 GPa or less, 6.5 GPa or less, or 6.3 GPa or less.
[0252] The method for measuring the complex elastic modulus of the fourth layer is the same as the method for measuring the complex elastic modulus of the second layer in the first embodiment.
[0253] (3) Indentation hardness H IT / Complex elastic modulus E r
[0254] The indentation hardness H of the fourth layer in this embodiment IT (MPa) relative to the composite elastic modulus E r (GPa) ratio (indentation hardness H IT / Complex elastic modulus E r ) is, for example, greater than 30, or may be greater than 40. On the other hand, for example, less than 85, or may be less than 70. IT / Complex elastic modulus E r If the H value is greater than the above value, the bending resistance tends to be good. It should be noted that in the case of a high-hardness material such as glass with a composite elastic modulus of about 70 GPa, IT When / Er is high, brittle fracture tends to occur easily. However, in the region where the complex elastic modulus is several GPa or less, if H IT When / Er is the above value or more, the bending resistance tends to be good.
[0255] It should be noted that the indentation hardness H IT The method for measuring the indentation hardness H of the second layer in the first embodiment IT The determination method is the same.
[0256] (4) Materials
[0257] The fourth layer preferably has a resin. The resin contained in the fourth layer is not particularly limited as long as it has transparency and impact absorption and the fourth layer has the above-mentioned recovery rate. Specifically, for example, polyimide resins, polyamide resins, polyester resins, cellulose resins, acrylic resins, polycarbonate resins, polyethylene naphthalate resins, urethane resins, vinyl chloride resins, vinyl acetate resins, epoxy resins, etc. These resins can be used alone or in combination of two or more.
[0258] In addition, in this specification, a polyimide-based resin refers to a polymer having an imide bond in the main chain. Examples of the polyimide-based resin include polyimide, polyamide-imide, polyester-imide, and polyether-imide.
[0259] The fourth layer may further contain additives as necessary. Examples of the additives include adhesion improvers, inorganic particles, organic particles, ultraviolet absorbers, antioxidants, light stabilizers, and surfactants.
[0260] As the formation method of the 4th layer, for example, a method of applying a resin composition on the 3rd layer can be cited. As a coating method, as long as it is a method that can be coated with a desired thickness, there is no particular limitation, and general coating methods such as gravure coating, reverse gravure coating, gravure offset coating, spin coating, roller coating, reverse roller coating, blade coating, dip coating, spray coating, die coating, screen printing can be cited. In addition, as the formation method of the 4th layer, a transfer method in which the 4th layer is transferred to the principal surface of the 3rd layer, and a method in which the 4th layer of film is laminated on the principal surface of the 3rd layer by an adhesive layer can also be used. In addition, before forming the 4th layer, the 1st principal surface S1 of the 4th layer side of the 3rd layer can be subjected to a corona treatment or the like to improve adhesion. The adhesion improvement process can also be carried out on the side SS of the 3rd layer described later.
[0261] (5) Others
[0262] The thickness of the fourth layer is, for example, preferably 5 μm or more, more preferably 10 μm or more, and particularly preferably 20 μm or more. On the other hand, it is preferably 80 μm or less, more preferably 70 μm or less, and particularly preferably 60 μm or less. Specifically, it is preferably in the range of 5 μm or more and 80 μm or less, more preferably in the range of 10 μm or more and 70 μm or less, and particularly preferably in the range of 20 μm or more and 60 μm or less. If the thickness of the fourth layer is too thick, the bending resistance may be impaired. On the other hand, if the thickness of the fourth layer is too thin, it may be impossible to ensure adhesion and peel off.
[0263] In the present embodiment, the total thickness of the second layer and the fourth layer is preferably 100 μm or less, more preferably 75 μm or less, and particularly preferably 50 μm or less.
[0264] like Figure 7 and Figure 8 As shown, the third layer 3 generally has a first main surface S1 on the fourth layer side, a second main surface S2 facing the first main surface S1, and a side surface SS different from the first main surface S1 and the second main surface S2. Figure 7 and Figure 8 As shown, when the third layer 3 is a glass substrate, the fourth layer 4 preferably covers the side surface SS of the third layer 3. In this case, the width W4 of the fourth layer 4 is larger than the width W3 of the third layer 3.
[0265] When the third layer is a glass substrate, the strength of the side surface of the glass substrate can be improved by covering the side surface of the third layer with the fourth layer. In addition, micro cracks on the side surface of the glass substrate can be filled with the fourth layer, thereby improving the strength of the side surface of the glass substrate. Thus, the impact resistance of the end of the glass laminate can be improved.
[0266] In addition, the degree of covering of the side surface of the third layer by the fourth layer is not particularly limited as long as the strength of the side surface of the third layer can be improved by covering the side surface of the third layer with the fourth layer. For example, the entire side surface of the third layer may be covered by the fourth layer, or only a portion of the side surface of the third layer may be covered by the fourth layer. Specifically, Figure 7 In the embodiment, the fourth layer 4 covers the entire side surface of the third layer 3. On the other hand, in Figure 8 In the embodiment, the fourth layer 4 covers a portion of the side surface of the third layer 3 .
[0267] As the thickness direction D T The degree of coverage of the side of the third layer by the fourth layer, specifically, the ratio (Tc4 / T3) of the thickness Tc4 of the side of the third layer covered by the fourth layer to the thickness T3 of the third layer is, for example, greater than 0.5, greater than 0.6, or greater than 0.7. On the other hand, it is, for example, less than 1.0, less than 0.9, or less than 0.8. Specifically, the above ratio (Tc4 / T3) is, for example, greater than 0.5 and less than 1.0, greater than 0.6 and less than 0.9, or greater than 0.7 and less than 0.8. By being within the above ratio range, the impact resistance of the side of the glass substrate becomes good.
[0268] The shape of the glass substrate is usually a rectangular parallelepiped, which is a hexahedron. In addition, for example, when the glass substrate is chamfered, the shape of the glass substrate is also usually a rectangular parallelepiped, which can be regarded as a roughly hexahedron. In this case, the glass substrate has a first face and a second face facing each other and four side faces. In this case, as the degree of coverage of the side face of the glass substrate by the second layer, at least one of the four side faces of the glass substrate is covered by the second layer. That is, in this case, one of the four side faces of the glass substrate may be covered by the fourth layer, two side faces may be covered by the fourth layer, three side faces may be covered by the fourth layer, or four side faces may be covered by the fourth layer.
[0269] Among them, it is preferred that two of the four side surfaces of the glass substrate that face each other are covered with the fourth layer, and it is preferred that two of the four side surfaces of the glass substrate that are substantially parallel to the bending direction of the glass laminate are covered with the second layer. This is because it is possible to suppress the generation of cracks at the bent portion when the glass laminate is bent, thereby improving the bending resistance.
[0270] 3. Layer 1
[0271] The details of the first layer are the same as those of the first layer in the first embodiment.
[0272] 4. Layer 3
[0273] The details of the third layer are the same as those of the third layer in the first embodiment.
[0274] 5. Other layers
[0275] The laminate in this embodiment may have other layers in addition to the above-mentioned first layer, second layer, fourth layer, and third layer. The display device component in this embodiment may further have a functional layer on the surface side of the first layer opposite to the third layer, or between the first layer and the second layer. Examples of the functional layer disposed on the surface side of the first layer opposite to the third layer include a hard coating layer, a protective layer, an anti-reflection layer, and an anti-glare layer. Examples of the functional layer disposed on the surface side of the first layer opposite to the third layer include a hard coating layer, a protective layer, an anti-reflection layer, and an anti-glare layer. Examples of the functional layer disposed between the first layer and the second layer include a decorative layer and a primer layer. For example, Fig. 9 As shown in FIG. 1 , the laminate in this embodiment preferably further has a hard coating layer 5 on the surface side of the first layer 1 opposite to the third layer 3. Fig.10 As shown in (a) of FIG. 1 , the laminate in this embodiment may have a primer layer 6 between the first layer 1 and the second layer 2. Fig.10 As shown in (b), the laminate in this embodiment may have a decorative layer 7 between the first layer 1 and the second layer 2. Fig.10 As shown in (c) of FIG. 1 , the laminate in this embodiment may include a decorative layer 7 and a primer layer 6 between the first layer 1 and the second layer 2 . In this case, the decorative layer 7 may be disposed between the primer layer 6 and the second layer 2 .
[0276] The details of these other layers are the same as those described in detail in the above-mentioned first embodiment.
[0277] 6. Characteristics of laminates
[0278] (1) Total light transmittance and haze
[0279] The total light transmittance and haze of the laminate in this embodiment may be the same as those of the laminate in the first embodiment.
[0280] (2) Bending resistance
[0281] The laminate in the present embodiment preferably has bending resistance. In particular, the laminate in the present embodiment preferably does not cause peeling of the second layer from the first layer and peeling of the fourth layer from the third layer in the above-mentioned clamshell bending test and U-shaped bending test.
[0282] (3) Peel strength
[0283] The laminated film in the present embodiment preferably has an adhesion evaluation result of 1 point or less between the third layer and the fourth layer by the cross cut method specified in JIS K 5600-5-6:1999.
[0284] The overview of the evaluation of the adhesion strength based on the cross-cutting method between the 3rd and 4th layers is as follows. First, an evaluation sample consisting of the 3rd and 4th layers is obtained. For the 4th layer of the evaluation sample, a cutter or the like is used to penetrate the 4th layer and cut into it to form a plurality of right-angled lattice patterns. At this time, it is preferred to use a cross-cutting fixture that can continuously and neatly form a plurality of right-angled lattice patterns. Next, an adhesive tape having an adhesive layer on one side such as a scotch tape for bonding is pasted in a manner covering all the lattices formed above. Then, the end of the pasted adhesive tape is grasped with a finger, peeled off from the 4th layer, and the peeling of the 4th layer is visually observed, and the results are classified according to the following evaluation criteria. Classification 0 is counted as 0 points, classification 1 is counted as 1 point, classification 2 is counted as 2 points, classification 3 is counted as 3 points, classification 4 is counted as 4 points, and classification 5 is counted as 5 points. Here, the size of one side of the lattice pattern is 2mm. It should be noted that in order to make the adhesive tape contact the fourth layer correctly, the adhesive tape was rubbed fully with the fingertips. The whole was visually confirmed to be neatly bonded. The adhesive tape was attached and peeled off within 5 minutes, and the end of the tape was grasped at an angle as close to 60° as possible and pulled apart reliably within about 0.5 seconds to 1.0 seconds.
[0285] Classification 0: The edges of the cut are completely smooth and there is no peeling in any of the holes of the grid.
[0286] Category 1: There is a small peeling of the coating film at the intersection of the cuts. However, the cross-cut portion affected will not exceed 5%.
[0287] Category 2: The coating peels off along the cut edges and / or at the intersections. Clearly more than 5% but not more than 15% of the cross-cut portion is affected.
[0288] Category 3: The coating peels off locally or completely along the cut edge and / or many parts of the mesh peel off locally or completely. The cross-cut part is clearly affected by more than 15%, but not more than 35%.
[0289] Category 4: The coating peels off locally or completely along the cut edge and / or peels off locally or completely at multiple locations. No more than 65% of the cross-cut portion is affected.
[0290] Category 5: Any degree of peeling that cannot be classified in Category 4.
[0291] The peel strength between the 4th layer and the 2nd layer of the laminate in this embodiment is, for example, 5N / 20mm width or more, 6N / 20mm width or more, or 10N / 20mm width or more. If the peel strength is above the above value, the adhesive force of the 2nd layer is sufficient, and the 2nd layer and the 4th layer are fully bonded to each other. On the other hand, the peel strength of the laminate is, for example, 50N / 20mm width or less, or 40N / 20mm width or less.
[0292] Here, the method for measuring the peel strength of the laminate in the present disclosure is as follows.
[0293] The peel strength can be measured by a 180-degree peel test according to JIS Z0237:2009. First, a test piece with a width of 20 mm and a length of 100 mm is cut out from the laminate. As a universal testing machine (tensile testing machine), "Autograph AG-X 1N (load sensor: SBL-1KN)" manufactured by Shimadzu Corporation is used. By a 180-degree peel test according to JIS Z0237:2009, peeling is performed at the interface of the second layer and the fourth layer under the conditions of a temperature of 25°C, a distance between the chucks of the tensile testing machine of 50 mm, a tensile speed of 300 mm / min, and a peeling angle of 180 degrees, and the peel strength is measured.
[0294] In addition, when the width of the test piece is not 20 mm, the peel strength (actually measured value) measured by the above-mentioned 180 degree peel test is converted into 20 mm width by the following formula.
[0295] Peel strength converted to 20 mm width [N / 20 mm] = measured value of peel strength [N / 20 mm] × 20 [mm] / width of test piece [mm]
[0296] 7. Application of laminate
[0297] The use of the laminate in this embodiment is the same as that of the laminate in the first embodiment.
[0298] B. Display device
[0299] The display device in the present disclosure includes a display panel and the laminated body disposed on the viewer side of the display panel.
[0300] Fig.11 1 is a schematic cross-sectional view showing an example of a display device in the present disclosure, which is an example of a laminated body. Fig.11As shown, the display device 20 includes a display panel 21 and a laminate 10 (laminate 10A of the first embodiment or laminate 10B of the second embodiment) disposed on the viewer side of the display panel 21. In the display device 20, the laminate 10 is used as a component disposed on the front of the display device 20, and an adhesive layer 22 is disposed between the laminate 10 and the display panel 21.
[0301] The laminate in the present disclosure may be the same as the laminate described above.
[0302] Examples of the display panel in the present disclosure include display panels used in display devices such as liquid crystal display devices, organic EL display devices, and LED display devices.
[0303] The display device in the present disclosure may include a touch component between the display panel and the laminate.
[0304] The display device in the present disclosure is preferably a flexible display. Among them, the display device in the present disclosure is preferably foldable. That is, the display device in the present disclosure is more preferably a foldable display. Since the display device in the present disclosure has the above-mentioned laminate, it has excellent impact resistance and bending resistance, and is suitable as a flexible display and further a foldable display.
[0305] C. Laminated body parts
[0306] The laminate component disclosed in the present invention is a laminate component used in the laminate described in "A-1. Laminate (First Embodiment)" or "A-2. Laminate (Second Embodiment)", and is formed by laminating the first layer and the second layer in "A-1. Laminate (First Embodiment)" or "A-2. Laminate (Second Embodiment)".
[0307] Fig.12 Schematic cross-sectional view of the laminate member in the present disclosure. Fig.12 The laminate member 15 shown has a first layer 1 and a second layer 2, and the recovery rate of the cross section of the second layer 2 by the nanoindentation method is 10% or more. Such a laminate member 15 is used to manufacture, for example Figure 1 The laminate 10A shown in the figure has the first layer 1, the second layer 2 and the third layer 3 in this order. Alternatively, such a laminate member 15 is used to manufacture, for example Figure 6 The laminate 10B shown has a first layer 1, a second layer 2, a fourth layer 4, and a third layer 3 in this order.
[0308] The laminate 10A is manufactured by closely contacting the surface of the second layer side of the laminate member in the present disclosure with a glass substrate or a resin substrate that becomes the third layer. In addition, the laminate 10B is manufactured by closely contacting the surface of the second layer side of the laminate member (first laminate member) in the present disclosure with the surface of the fourth layer side of the second laminate member having the fourth layer and the third layer. According to such a laminate member, a laminate having excellent bending resistance can be obtained for the above reasons.
[0309] The first layer, the second layer, the third layer, and the fourth layer are the same as the first layer, the second layer, the third layer, and the fourth layer in the above-mentioned "A-1. Laminated body (first embodiment)" and "A-2. Laminated body (second embodiment)".
[0310] It should be noted that the present disclosure is not limited to the above-mentioned embodiments. The above-mentioned embodiments are illustrative, and any other embodiments having substantially the same configuration as the technical concept described in the claims of the present disclosure and having the same effects are included in the technical scope of the present disclosure.
[0311] Example
[0312] Hereinafter, the present disclosure will be further described by showing examples and comparative examples.
[0313] <First Embodiment>
[0314] [Comparative Example]
[0315] (Production of Laminated Body Components)
[0316] First, a 50 μm thick PET film was prepared as the first layer. On one surface of the PET film, the following hard coat curable resin composition was applied to a predetermined thickness, dried at 80° C. for 3 minutes, and cured by ultraviolet irradiation to form a 10 μm thick hard coat layer.
[0317] The curable resin composition for a hard coat layer was prepared by mixing the respective components so as to have the composition shown below.
[0318] · A mixture of dipentaerythritol pentaacrylate and dipentaerythritol hexaacrylate (M403, manufactured by Toagosei Co., Ltd.) 25 parts by mass
[0319] · Dipentaerythritol EO-modified hexaacrylate (A-DPH-6E, manufactured by Shin-Nakamura Chemical Co., Ltd.) 25 parts by mass
[0320] · 50 parts by mass of irregular silicon dioxide fine particles (average particle size 25 nm, manufactured by JGC Catalysts & Chemicals Co., Ltd.) (solid equivalent)
[0321] · Photopolymerization initiator (Irg184) 4 parts by mass
[0322] Fluorine-based leveling agent (F568, manufactured by DIC Corporation) 0.2 parts by mass (solid equivalent)
[0323] Ultraviolet light absorber 1 (DAinsorb P6, manufactured by Yamato Chemical) 3 parts by mass
[0324] Solvent (MIBK) 150 parts by mass
[0325] Next, the second layer composition A was applied to the other side of the PET film and dried to form a bonding layer A (second layer) with a thickness of 5 μm. Thus, a laminate member including the first layer and the second layer was obtained. Next, the second layer side surface of the laminate member was brought into close contact with a glass substrate (chemically strengthened glass, thickness 30 μm), heat-fused, and then aged to produce a laminate having the first layer, the second layer, and the third layer.
[0326] The second layer composition A was prepared by mixing the respective components so as to have the composition shown below.
[0327] (Composition A for the second layer)
[0328] · Amorphous polyester resin (Mw 16,000, Tg 7°C, tensile elongation at break 1%) 100 parts by mass
[0329] 5 parts by mass of hexamethylene diisocyanate (Coronate 2203, manufactured by Nippon Polyurethane Industries, Ltd.)
[0330] Silane coupling agent (KBM-403, manufactured by Shin-Etsu Chemical Co., Ltd.) 5 parts by mass
[0331] Fluorine-based leveling agent (F568, manufactured by DIC Corporation) 0.2 parts by mass
[0332] Solvent (MEK) 310 parts by mass
[0333] Solvent (toluene) 310 parts by mass
[0334] [Example 1-1]
[0335] A laminate was produced by the same method as in the comparative example except that the second layer composition B was used instead of the second layer composition A to form the bonding layer B (second layer).
[0336] The second layer composition B was prepared by mixing the respective components so as to have the composition shown below.
[0337] (Composition B for the second layer)
[0338] Polyether urethane resin (Tg-45°C), 100 parts by mass
[0339] 5 parts by mass of hexamethylene diisocyanate (Coronate 2203, manufactured by Nippon Polyurethane Industries, Ltd.)
[0340] Silane coupling agent (KBM-403, manufactured by Shin-Etsu Chemical Co., Ltd.) 5 parts by mass
[0341] Fluorine-based leveling agent (F568, manufactured by DIC Corporation) 0.2 parts by mass
[0342] Solvent (MEK) 310 parts by mass
[0343] Solvent (toluene) 310 parts by mass
[0344] [Example 1-2]
[0345] A laminate was produced by the same method as in the comparative example except that the second layer composition C was used instead of the second layer composition A to form the bonding layer C (second layer).
[0346] The second layer composition C was prepared by mixing the respective components so as to have the composition shown below.
[0347] (Composition C for the second layer)
[0348] · Amorphous polyester resin (Mw 16,000, Tg 65°C, tensile elongation at break 3%) 100 parts by mass
[0349] 5 parts by mass of hexamethylene diisocyanate (Coronate 2203, manufactured by Nippon Polyurethane Industries, Ltd.)
[0350] Silane coupling agent (KBM-403, manufactured by Shin-Etsu Chemical Co., Ltd.) 5 parts by mass
[0351] Fluorine-based leveling agent (F568, manufactured by DIC Corporation) 0.2 parts by mass
[0352] Solvent (MEK) 310 parts by mass
[0353] Solvent (toluene) 310 parts by mass
[0354] [Examples 1-3]
[0355] A laminate was produced by the same method as in the comparative example except that the second layer composition D was used instead of the second layer composition A to form the bonding layer D (second layer).
[0356] The second layer composition D was prepared by mixing the respective components so as to have the composition shown below.
[0357] (Composition D for the second layer)
[0358] 100 parts by mass of amorphous polyester resin (Mw 16,000, Tg 20°C, tensile elongation at break 1100%)
[0359] 5 parts by mass of hexamethylene diisocyanate (Coronate 2203, manufactured by Nippon Polyurethane Industries, Ltd.)
[0360] Silane coupling agent (KBM-403, manufactured by Shin-Etsu Chemical Co., Ltd.) 5 parts by mass
[0361] Fluorine-based leveling agent (F568, manufactured by DIC Corporation) 0.2 parts by mass
[0362] Solvent (MEK) 310 parts by mass
[0363] Solvent (toluene) 310 parts by mass
[0364] [Examples 1-4]
[0365] A laminate was produced by the same method as in the comparative example except that the second layer composition E was used instead of the second layer composition A to form the bonding layer E (second layer).
[0366] The second layer composition E was prepared by mixing the respective components so as to have the composition shown below.
[0367] (Composition E for the second layer)
[0368] · Amorphous polyester resin (Tg 1°C, tensile elongation at break 1000%) 100 parts by mass
[0369] 5 parts by mass of hexamethylene diisocyanate (Coronate 2203, manufactured by Nippon Polyurethane Industries, Ltd.)
[0370] Silane coupling agent (KBM-403, manufactured by Shin-Etsu Chemical Co., Ltd.) 5 parts by mass
[0371] Fluorine-based leveling agent (F568, manufactured by DIC Corporation) 0.2 parts by mass
[0372] Solvent (MEK) 310 parts by mass
[0373] Solvent (toluene) 310 parts by mass
[0374] [Examples 1-5]
[0375] A laminate was produced by the same method as in the comparative example except that the second layer composition F was used instead of the second layer composition A to form the bonding layer F (second layer).
[0376] The second layer composition F was prepared by mixing the respective components so as to have the composition shown below.
[0377] (Composition F for the second layer)
[0378] · Amorphous polyester resin (Mw 16,000, Tg 40°C, tensile elongation at break 3%) 100 parts by mass
[0379] 5 parts by mass of hexamethylene diisocyanate (Coronate 2203, manufactured by Nippon Polyurethane Industries, Ltd.)
[0380] Silane coupling agent (KBM-403, manufactured by Shin-Etsu Chemical Co., Ltd.) 5 parts by mass
[0381] Fluorine-based leveling agent (F568, manufactured by DIC Corporation) 0.2 parts by mass
[0382] Solvent (MEK) 310 parts by mass
[0383] Solvent (toluene) 310 parts by mass
[0384] [Examples 1-6]
[0385] A laminate was produced by the same method as in the comparative example except that the second layer composition G was used instead of the second layer composition A to form the bonding layer G (second layer).
[0386] The second layer composition G was prepared by mixing the respective components so as to have the composition shown below.
[0387] (Composition G for the second layer)
[0388] · Modified polyolefin resin (Tg 0°C or less) 100 parts by mass
[0389] 5 parts by mass of hexamethylene diisocyanate (Coronate 2203, manufactured by Nippon Polyurethane Industries, Ltd.)
[0390] Silane coupling agent (KBM-403, manufactured by Shin-Etsu Chemical Co., Ltd.) 5 parts by mass
[0391] Fluorine-based leveling agent (F568, manufactured by DIC Corporation) 0.2 parts by mass
[0392] Solvent (MEK) 310 parts by mass
[0393] Solvent (toluene) 310 parts by mass
[0394] [Examples 1-7]
[0395] A laminate was produced by the same method as in the comparative example except that the second layer composition H was used instead of the second layer composition A to form the bonding layer H (second layer).
[0396] The second layer composition H was prepared by mixing the respective components so as to have the following composition.
[0397] (Composition H for the second layer)
[0398] · Polyester resin (Tg 70°C, tensile elongation at break 2%) 100 parts by mass
[0399] 5 parts by mass of hexamethylene diisocyanate (Coronate 2203, manufactured by Nippon Polyurethane Industries, Ltd.)
[0400] Silane coupling agent (KBM-403, manufactured by Shin-Etsu Chemical Co., Ltd.) 5 parts by mass
[0401] Fluorine-based leveling agent (F568, manufactured by DIC Corporation) 0.2 parts by mass
[0402] Solvent (MEK) 310 parts by mass
[0403] Solvent (toluene) 310 parts by mass
[0404] [Examples 1-8]
[0405] A laminate was produced in the same manner as in Comparative Example except that a 50 μm thick adhesive layer (acrylic pressure-sensitive adhesive sheet, OCA, Tg-9° C.) (8146-2 manufactured by 3M) was laminated as the second layer using a hand roller to form an adhesive layer I.
[0406] [Examples 1-9]
[0407] A laminate was produced in the same manner as in Comparative Example except that a 10 μm thick adhesive layer (acrylic pressure-sensitive adhesive sheet, OCA, Tg-8° C.) (“Panaclean PD-S1” manufactured by PANAC) was laminated as the second layer using a hand roller to form an adhesive layer J.
[0408] [Examples 1-10]
[0409] A laminate was produced by the same method as in the comparative example except that the second layer composition K was used instead of the second layer composition A to form the bonding layer K (second layer).
[0410] The second layer composition K was prepared by mixing the respective components so as to have the composition shown below.
[0411] (Composition K for the second layer)
[0412] Polyester urethane resin (UR-8300, solid content 30%, manufactured by Toyobo Co., Ltd.) 100 parts by mass
[0413] Hexamethylene diisocyanate (Coronate 2203, manufactured by Nippon Polyurethane Industries, Ltd.) 1.5 parts by mass
[0414] Silane coupling agent (KBM-403, manufactured by Shin-Etsu Chemical Co., Ltd.) 1.5 parts by mass
[0415] Fluorine-based leveling agent (F568, manufactured by DIC Corporation) 0.2 parts by mass (solid equivalent)
[0416] Solvent (MEK) 58 parts by mass
[0417] Solvent (toluene) 58 parts by mass
[0418] [Examples 1-11]
[0419] A laminate was produced by the same method as in the comparative example except that the second layer composition L was used instead of the second layer composition A to form the bonding layer L (second layer).
[0420] The second layer composition L was prepared by mixing the respective components so as to have the composition shown below.
[0421] (Composition L for the second layer)
[0422] Polyester urethane resin (UR-5537, solid content 30%, manufactured by Toyobo Co., Ltd.) 100 parts by mass
[0423] Hexamethylene diisocyanate (Coronate 2203, manufactured by Nippon Polyurethane Industries, Ltd.) 1.5 parts by mass
[0424] Silane coupling agent (KBM-403, manufactured by Shin-Etsu Chemical Co., Ltd.) 1.5 parts by mass
[0425] Fluorine-based leveling agent (F568, manufactured by DIC Corporation) 0.2 parts by mass (solid equivalent)
[0426] Solvent (MEK) 58 parts by mass
[0427] Solvent (toluene) 58 parts by mass
[0428] [Examples 1-12]
[0429] The laminate was manufactured by the same method as in the comparative example except that the bonding layer D (second layer) was formed in a manner covering the side of the third layer by using the second layer composition D instead of the second layer composition A. At this time, the ratio (Tc2 / T3) of the thickness Tc2 of the side of the third layer covered by the second layer to the thickness T3 of the third layer was 0.7.
[0430] (1) Determination of recovery rate
[0431] The recovery rate of the cross section of the second layer of the obtained laminate was measured by the above-mentioned recovery rate measurement method based on the nanoindentation method.
[0432] (2) Determination of complex elastic modulus
[0433] The complex elastic modulus of the cross section of the second layer of the obtained laminate was measured by the above-mentioned method for measuring the complex elastic modulus of the cross section of the second layer.
[0434] (3) Indentation hardness H IT / Complex elastic modulus E r
[0435] The indentation hardness H of the obtained laminate passing through the cross section of the second layer is IT The indentation hardness H of the cross section of the second layer is measured by the method of IT (MPa), calculate the indentation hardness H IT Relative to the composite elastic modulus E r (GPa) ratio (indentation hardness H IT / Complex elastic modulus E r The results are shown in Table 1.
[0436] [evaluate]
[0437] (1) Clamshell bend test (CS bend test)
[0438] The obtained laminate was subjected to a dynamic bending test by the above-mentioned clamshell bending test. The laminate was bent 200,000 times at a curvature radius R to confirm whether the second layer of the laminate was peeled off and evaluated according to the following criteria. At this time, the laminate was bent in such a way that the hard coating layer was on the inside and the glass substrate was on the outside.
[0439] Evaluation Benchmarks
[0440] A: No change after bending 200,000 times at R1.25mm
[0441] B: No change after bending 200,000 times with R1.5mm
[0442] C: No change after bending 200,000 times at R2.0mm
[0443] D: After bending 200,000 times at R2.0mm, the second layer peeled off
[0444] (2) U-shaped bending test
[0445] The obtained laminate was subjected to a dynamic bending test by the above-mentioned U-shaped bending test to evaluate the bending resistance of the laminate. At this time, the laminate was bent in such a way that the hard coating layer became the inner side and the glass substrate became the outer side, and the curvature radius R was set to 1.5 mm. The results of the dynamic bending test were evaluated according to the following criteria.
[0446] A: No change after bending 200,000 times with R1.5mm
[0447] D: After bending 200,000 times at R1.5mm, the second layer peeled off
[0448] (3) Peel strength measurement
[0449] The peel strength of the obtained laminate was measured by the above-mentioned method.
[0450] (4) End impact test
[0451] The obtained laminate was subjected to Fig.16 The impact test is shown in the example. First, the sample table 31 and the track 32 are arranged to be inclined at 16° relative to the horizontal plane. Next, the laminate 10 is placed on the sample table 31, and the weight 33 is placed on the laminate 10 to fix the laminate 10. At this time, the laminate 10 is fixed in such a way that the end of the laminate 10 protrudes 2 mm from the side of the sample table 31. Next, 5.5 g, The steel ball 34 falls from a predetermined distance L along the track 32 and collides with the side of the laminate 10. Then, at the end of the laminate 10, the maximum distance L at which the laminate 10 does not crack or break is measured and evaluated according to the following evaluation criteria. It should be noted that the larger the value, the higher the impact resistance.
[0452] A: 30cm or more
[0453] B: less than 30cm
[0454] [Table 1]
[0455]
[0456] As shown in Table 1, in Examples 1-1 to 1-12 in which the recovery rate of the cross section of the second layer based on the nanoindentation method is 10% or more, good bending resistance is confirmed in the clamshell bending test in addition to the U-shaped bending test. On the other hand, in the comparative example in which the recovery rate of the cross section of the second layer based on the nanoindentation method is less than 10%, insufficient bending resistance is confirmed in the clamshell bending test. In addition, for example, when comparing Example 1-3 and the comparative example, it is confirmed that although the value of the complex elastic modulus is close, the evaluation results of the clamshell bending test are different. When comparing Example 1-12 and Example 1-3, Example 1-12, in which the side of the third layer is covered with the second layer, has good end impact resistance.
[0457] <Second Embodiment>
[0458] [Example 2-1]
[0459] (Production of Laminated Body Components)
[0460] First, a 50 μm thick PET film was prepared as the first layer. The hard coat curable resin composition was applied to one surface of the PET film to a predetermined thickness, dried at 80° C. for 3 minutes, and cured by ultraviolet irradiation to form a 10 μm thick hard coat layer.
[0461] Next, the second layer composition D was applied to the other side of the PET film and dried to form a 5 μm thick bonding layer D (second layer). Thus, a laminate member (first laminate member) including the first and second layers was obtained.
[0462] Next, the following resin composition for the fourth layer was applied in a manner covering one main surface of the glass substrate (chemically strengthened glass, thickness 30 μm) as the third layer and the side of the third layer to form a fourth layer with a thickness of 5 μm. At this time, the ratio (Tc4 / T3) of the thickness Tc4 of the side of the third layer covered by the fourth layer to the thickness T3 of the third layer was 0.3. Thus, the second component for the laminate was obtained. It should be noted that the glass substrate as the third layer was subjected to corona treatment (100 W, 3 mm / min) as a pre-treatment.
[0463] (Resin composition for the fourth layer)
[0464] Polyester urethane resin (UR-5537, solid content 30%, manufactured by Toyobo Co., Ltd.) 50 parts by mass
[0465] 50 parts by mass of a mixture of dipentaerythritol pentaacrylate and dipentaerythritol hexaacrylate (M403, manufactured by Toagosei Co., Ltd.)
[0466] · Ommirad184 4 parts by weight
[0467] Silane coupling agent (KBM-403, manufactured by Shin-Etsu Chemical Co., Ltd.) 1.5 parts by mass
[0468] Fluorine-based leveling agent (F568, manufactured by DIC Corporation) 0.2 parts by mass (solid equivalent)
[0469] Solvent (MEK) 58 parts by mass
[0470] Solvent (toluene) 58 parts by mass
[0471] Next, the second layer side surface of the first laminate component and the fourth layer side surface of the second laminate component are brought into close contact, heat-fused, and then aged to produce a laminate having the first, second, fourth and third layers.
[0472] [Example 2-2]
[0473] A laminate was produced by the same method as in Example 2-1 except that the ratio (Tc4 / T3) of the thickness Tc4 of the side surface of the third layer covered with the fourth layer to the thickness T3 of the third layer was set to 0.9.
[0474] [Example 2-3]
[0475] A laminate was produced in the same manner as in Example 2-1 except that the thickness of the fourth layer was 25 μm and the ratio (Tc4 / T3) of the thickness Tc4 of the side surface of the third layer covered by the fourth layer to the thickness T3 of the third layer was 0.7.
[0476] [Examples 2-4]
[0477] A laminate was produced in the same manner as in Example 2-1 except that the thickness of the fourth layer was 50 μm and the ratio (Tc4 / T3) of the thickness Tc4 of the side surface of the third layer covered by the fourth layer to the thickness T3 of the third layer was 0.6.
[0478] The obtained laminate was subjected to the above-mentioned (1) clamshell bending test (CS bending test), (2) U-shaped bending test, (3) peel strength measurement and (4) edge impact test. The results are shown in Table 2.
[0479] [Table 2]
[0480]
[0481] As shown in Table 2, in Examples 2-1 to 2-4, in which the recovery rate of the cross section of each of the second layer and the fourth layer based on the nanoindentation method was 10% or more, good bending resistance was confirmed in the clamshell bending test in addition to the U-shaped bending test. In addition, it was confirmed that Examples 2-2 to 2-4, in which (Tc4 / T3) was 0.5 or more, had good end impact resistance compared to Example 2-1.
[0482] That is, the present disclosure can provide the following solutions. [1]
[0484] A laminate comprising a first layer, a second layer and a third layer in this order, wherein:
[0485] The recovery rate of the cross section of the second layer measured by a nanoindentation method is 10% or more. [2]
[0487] The laminate according to [1], wherein the complex elastic modulus of the second layer is greater than 0.05 GPa. [3]
[0489] The laminate according to [1] or [2], wherein the thickness of the second layer is 1 μm to 25 μm. [4]
[0491] The laminate according to any one of [1] to [3], wherein the third layer is a glass substrate having a film thickness in the range of 15 μm to 115 μm. [5]
[0493] The laminate according to any one of [1] to [4], wherein the first layer is a resin film. [6]
[0495] The laminate according to any one of [1] to [5], wherein a hard coating layer is provided on the surface of the first layer opposite to the second layer side. [7]
[0497] The laminate according to any one of [1] to [6], which is used as a front panel of a display device. [8]
[0499] A laminate comprising a first layer, a second layer, a fourth layer and a third layer in this order, wherein:
[0500] The recovery rate of each cross section of the second layer and the fourth layer by a nanoindentation method is 10% or more. [9]
[0502] The laminate according to [8], wherein the third layer has a first main surface located on the fourth layer side, a second main surface facing the first main surface, and a side surface different from the first main surface and the second main surface,
[0503] The fourth layer covers the side surface of the third layer.
[10]
[0505] The laminate according to [9], wherein a ratio of the thickness of the side surface covered with the fourth layer to the thickness of the third layer is 0.5 to 1.0.
[11]
[0507] The laminate according to any one of [8] to
[10] , wherein the complex elastic modulus of the second layer is greater than 0.05 GPa.
[12]
[0509] The laminate according to any one of [8] to
[11] , wherein the complex elastic modulus of the fourth layer is greater than 0.05 GPa.
[13]
[0511] The laminate according to any one of [8] to
[12] , wherein the second layer has a thickness of 1 μm to 25 μm.
[14]
[0513] The laminate according to any one of [8] to
[13] , wherein the thickness of the fourth layer is 5 μm or more and 80 μm or less.
[15]
[0515] The laminate according to any one of [8] to
[14] , wherein the third layer is a glass substrate having a film thickness in the range of 15 μm to 115 μm.
[16]
[0517] The laminate according to any one of [8] to
[15] , wherein the first layer is a resin film.
[17]
[0519] The laminate according to any one of [8] to
[16] , wherein a hard coating layer is provided on the surface of the first layer opposite to the second layer side.
[18]
[0521] The laminate according to any one of [8] to
[17] , which is used as a front panel of a display device.
[19]
[0523] A display device comprising:
[0524] display panel; and
[0525] The laminate according to any one of [1] to
[18] , which is arranged on the viewer side of the display panel.
[20]
[0527] A laminate component, which is used for the laminate described in any one of [1] to
[18] , wherein:
[0528] The laminate member is formed by laminating the first layer and the second layer.
[0529] Description of Reference Numerals
[0530] 1…Layer 1
[0531] 2…Layer 2
[0532] 3…3rd floor
[0533] 4…4th layer
[0534] 5…Hard coating
[0535] 6…Base coating
[0536] 7…Decorative layer
[0537] 10...laminated body
[0538] 20…Display device
[0539] 21…Display Panel
Claims
1. A laminate comprising a first layer, a second layer and a third layer in this order, wherein: The recovery rate of the cross section of the second layer by a nanoindentation method is 10% or more.
2. The laminate according to claim 1, wherein The complex elastic modulus of the second layer is greater than 0.05 GPa.
3. The laminate according to claim 1, wherein The thickness of the second layer is not less than 1 μm and not more than 25 μm.
4. The laminate according to claim 1, wherein The third layer is a glass substrate having a film thickness in the range of 15 μm to 115 μm.
5. The laminate according to claim 1, wherein The first layer is a resin film.
6. The laminate according to claim 1, wherein A hard coating layer is provided on the surface of the first layer opposite to the second layer side.
7. The laminate according to claim 1, which is used as a front panel of a display device.
8. A laminate comprising a first layer, a second layer, a fourth layer and a third layer in this order, wherein: The recovery rate of each cross section of the second layer and the fourth layer by a nanoindentation method is 10% or more.
9. The laminate according to claim 8, wherein The third layer has a first main surface located on the fourth layer side, a second main surface facing the first main surface, and a side surface different from the first main surface and the second main surface. The fourth layer covers the side surface of the third layer.
10. The laminate according to claim 9, wherein A ratio of the thickness of the side surface covered with the fourth layer to the thickness of the third layer is 0.5 or more and 1.0 or less.
11. The laminate according to claim 8, wherein The complex elastic modulus of the second layer is greater than 0.05 GPa.
12. The laminate according to claim 8, wherein The composite elastic modulus of the fourth layer is greater than 0.05 GPa.
13. The laminate according to claim 8, wherein The thickness of the second layer is not less than 1 μm and not more than 25 μm.
14. The laminate according to claim 8, wherein The thickness of the fourth layer is not less than 5 μm and not more than 80 μm.
15. The laminate according to claim 8, wherein The third layer is a glass substrate having a film thickness in the range of 15 μm to 115 μm.
16. The laminate according to claim 8, wherein The first layer is a resin film.
17. The laminate according to claim 8, wherein A hard coating layer is provided on the surface of the first layer opposite to the second layer side.
18. The laminate according to claim 8, which is used as a front panel of a display device.
19. A display device comprising: display panel; and The laminate according to any one of claims 1 to 18, which is arranged on the observer side of the display panel.
20. A laminate component for use in the laminate according to any one of claims 1 to 18, wherein: The laminate member is formed by laminating the first layer and the second layer.
Citation Information
Patent Citations
Polyimide film, polyimide, polyimide precursor, laminate, and surface material for displays
JP2018104682A
Optical laminate and display device
JP2021140147A
Flexible cover plate and preparation method thereof, and display panel and preparation method thereof
CN113257129A
Anti-glare film, method for designing anti-glare film, method for manufacturing anti-glare film, optical member, and image display device
CN114651197A
Laminated body and display device using the laminated body
CN1462237A